Pha bio-based antistatic low-dust barrier packaging material for clean isolation of semiconductor and electronic components and preparation method, system and application thereof
Patent Information
- Application Number
- CN202611398475.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-10
- Publication Date
- 2026-10-13
AI Technical Summary
若仅保留WPU空白区,湿热处理后切边附近的疏水保持和纤维固定能力可能不足
[0081]本发明在两个主表面的跨面错相功能映射过渡区内设置错位的含炭耗散图案,并使位于一个主表面的含炭耗散图案与位于相对主表面的PHA/WPU无炭固纤图案形成跨面对应,由此减少两个主表面的含炭区域在同一厚向位置发生重叠的程度,降低双面含炭区域形成局部刚性叠加、摩擦掉粉和弯折开裂的风险。
Smart Images

Figure CN122899089A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical fields of clean turnover packaging for semiconductors and electronic components, paper-based functional materials, and electrostatic protection materials. It relates to PHA bio-based antistatic and low-dust barrier packaging materials for clean isolation of semiconductors and electronic components, as well as their preparation methods, systems, and applications. Background Technology
[0002] During the packaging, testing, assembly, inter-process transfer, and inter-factory transportation of semiconductor devices, sensors, connectors, printed circuit board modules, and other electronic components, it is necessary to control the risk of electrostatic discharge (ESD) and reduce contamination from packaging materials, such as paper fibers, fillers, coating particles, and conductive particles. For packaged devices already carried by trays, tubing, carrier tapes, or boxes, the external conductive container typically serves as a grounding, ESD discharge, and mechanical protection unit. However, it still requires internal linings, spacers, dividers, or sleeves to reduce friction, collisions, and localized contact contamination between the device and the container.
[0003] Ordinary paper-based liners are characterized by low cost, easy processing, and replaceability. However, porous fiber paper substrates are prone to releasing fibers and fine particles during die-cutting, slitting, insertion, bending, and repeated handling. If a conductive carbon black coating is directly applied to the paper surface, the conductive carbon black can form an electronic conductive network that does not rely on hygroscopic small molecules. However, when the carbon-containing area is close to the final cut edge, die-cutting offset, lateral expansion of the coating, paper surface penetration, and bending cracks may expose the conductive carbon black on the cut surface or transfer it to the contact surface.
[0004] Antistatic paper relying on quaternary ammonium salts, ionic surfactants, or other hygroscopic small molecules can reduce surface resistance in medium to high humidity environments, but may experience increased resistance, migration of substances, and increased extractable ions at low relative humidity. For cleanroom isolation applications involving semiconductors and electronic components, the main electrostatic dissipation region forms an in-plane dissipation path through an electronically conductive phase immobilized in the film-forming polymer, while simultaneously maintaining a carbon-free and low-particle state in the final cut edge region.
[0005] US20040118538A1 discloses low-shedding, low-dust-shedding antistatic or electrostatic dissipative paper for cleanroom and electronic product packaging, wherein the dissipative component may include carbon materials, conductive polymers, or ionic polymers; EP0114802B2 discloses packaging materials using flexible open-pore fabric as a carrier and employing a polymer conductive layer containing conductive carbon black or graphite. The above documents relate to low-dust electrostatic dissipative materials, but do not disclose cross-surface quantitative mapping between double-sided carbon-containing dissipative patterns and the opposite PHA / WPU carbon-free solid fiber patterns, waterborne polyurethane flexible carbon-free buffer zones, and double-sided carbon-free terminal corridors.
[0006] DE10130919A1 discloses a method for reducing edge particle escape by impregnating a predetermined cutting area with a curable liquid; US20070141249A1 discloses the registration manufacturing of double-sided patterns for continuous rolls; US6146694A discloses double-sided segmented coating edge misalignment; US7511855B2 discloses a gradient transition between coated and uncoated areas. These technologies relate to edge sealing, double-sided registration, coating misalignment, or boundary gradients, but they do not establish a cross-face correspondence between the carbon-containing dissipative pattern and the opposite carbon-free fiber-fixed pattern, nor do they combine independent waterborne polyurethane buffer zones, double-sided carbon-free terminal corridors, and final edge cutting positions.
[0007] JP5795824B2 and its family of publications disclose a random metal grid on the surface of a transparent conductive film and the division of conductive and insulating regions, but do not involve paper-based double-sided functional coatings, cross-surface mapping of carbon-containing and carbon-free fiber-bonded regions, or die-cutting within double-sided carbon-free terminal corridors.
[0008] Polyhydroxy fatty acid esters (PHAs) are a type of polyester synthesized by microorganisms. They can be classified into short-chain PHAs and medium-to-long-chain PHAs according to the number of carbon atoms in the repeating units of hydroxy fatty acids. The repeating units of short-chain PHAs usually contain 3 to 5 carbon atoms, while the repeating units of medium-to-long-chain PHAs usually contain 6 to 14 carbon atoms.
[0009] If a large area of isotopic carbon-containing layer is formed on both sides of the paper substrate, the same position on both sides will simultaneously have high carbon black load and local coating rigidity, which will easily lead to thick-axis rigidity superposition during bending or die-cutting. If only a single ordinary carbon-free fiber-fixing strip is set, the lateral expansion of carbon-containing ink, paper swelling and shrinkage due to moisture, and die-cutting position offset may compress the actual safe distance. In some embodiments, waterborne polyurethane (WPU) is used as the continuous film-forming phase in this invention. If the PHA / WPU layer is continuously widened to the vicinity of the main carbon-containing region, the wider PHA-rich area may increase local hard ridges and bending cracks. If only the WPU blank area is retained, the hydrophobic retention and fiber fixation ability near the cut edge after hydrothermal treatment may be insufficient.
[0010] Therefore, there is a need for a paper-based packaging material that can be implemented on existing double-sided water-based coating, printing, drying and die-cutting equipment, which integrates carbon-containing electrostatic dissipation, cross-sided double carbon-containing prevention, flexible error buffering, PHA wet heat fiber fixation and carbon-free cutting edges, and maintains low moisture electrostatic dissipation and low dust clean isolation when double-sided registration deviation, carbon-containing boundary expansion, die-cutting offset, wet heat, bending and friction coexist. Summary of the Invention
[0011] The purpose of this invention is to overcome the shortcomings of the prior art and provide a PHA bio-based antistatic and low-dust barrier packaging material for clean isolation of semiconductors and electronic components, as well as its preparation method, system and application. It aims to solve the problems of carbon exposure on the cut surface, black transfer, release of paper fiber or coating particles, cracking and delamination of paper-based electrostatic dissipative liners under low humidity, double-sided registration deviation, carbon boundary expansion, paper swelling and shrinkage, die-cutting offset and humid heat bending conditions.
[0012] In some embodiments, the PHA is composed of one or more repeating units of hydroxy fatty acids containing 3 to 14 carbon atoms, including one or more short-chain PHAs and medium- to long-chain PHAs.
[0013] In embodiments employing short-chain PHA, the short-chain PHA is selected from one or more of poly(3-hydroxybutyrate), poly(4-hydroxybutyrate), poly(3-hydroxyvalerate), poly(3-hydroxybutyrate-3-hydroxyvalerate) copolyester (PHBV), and poly(3-hydroxybutyrate-4-hydroxybutyrate) copolyester.
[0014] In embodiments employing medium- to long-chain PHA, the medium- to long-chain PHA is selected from one or more of poly(3-hydroxyhexanoate), poly(3-hydroxyheptanoate), poly(3-hydroxyoctanoate), poly(3-hydroxynonanoate), poly(3-hydroxydecanoate), poly(3-hydroxyundecanoate), poly(3-hydroxydodecanate), poly(3-hydroxytetrate), poly(3-hydroxytetradecanoate), poly(3-hydroxytetradecanoate), and poly(3-hydroxybutyrate-3-hydroxyhexanoate) copolyester.
[0015] The embodiments in this specification use PHBV to prepare carbon-free solid fiber ink and carbon-free terminal corridors to verify the compatibility between the cross-plane phase-shifting functional mapping structure, the waterborne polyurethane flexible carbon-free buffer zone, and the polyhydroxyalkanoate / waterborne polyurethane carbon-free terminal corridor.
[0016] The packaging material provided by this invention includes a porous fiber paper substrate, which has a first main surface, a second main surface, and at least one finished trimmed edge. The first and second main surfaces are respectively provided with a continuous aqueous polyurethane fiber-sealing underlayer, an electrostatic dissipation main region formed on the aqueous polyurethane fiber-sealing underlayer, and a decoupling corridor located between the electrostatic dissipation main region and the finished trimmed edge. The electrostatic dissipation main region contains aqueous polyurethane and conductive carbon black, and forms an in-plane electrostatic dissipation path on its respective main surface.
[0017] Each of the decoupling corridors, along the direction from the main electrostatic dissipation region toward the final cut edge of the finished product, sequentially includes a cross-plane phase-shifting functional mapping transition region, a waterborne polyurethane flexible carbon-free buffer zone, and a polyhydroxyalkanoate / waterborne polyurethane carbon-free terminal corridor. For ease of description, the in-plane direction from the main electrostatic dissipation region toward the final cut edge of the finished product is defined as the corridor width direction, and the in-plane direction parallel to the final cut edge of the finished product is defined as the cut edge extension direction.
[0018] The cross-plane phase-shifting functional mapping transition regions of the first and second main surfaces are respectively provided with carbon-containing dissipation patterns continuously connected to the electrostatic dissipation main regions of their respective main surfaces, and polyhydroxyalkanoate / waterborne polyurethane carbon-free solid fiber patterns located outside the carbon-containing dissipation patterns. The carbon-containing dissipation patterns contain waterborne polyurethane and conductive carbon black, and the polyhydroxyalkanoate / waterborne polyurethane carbon-free solid fiber patterns contain polyhydroxyalkanoate and waterborne polyurethane, but do not contain conductive carbon black added as a functional component.
[0019] The carbon-containing dissipation patterns located on the first and second main surfaces are staggered along the tangential extension direction. The carbon-containing dissipation pattern on the first main surface and the polyhydroxyalkanoate / waterborne polyurethane carbon-free fiber-fixed pattern on the second main surface form a cross-face correspondence.
[0020] Neither the carbon-containing dissipation pattern nor the polyhydroxyalkanoate / waterborne polyurethane carbon-free fiber-bonded pattern extends into the waterborne polyurethane flexible carbon-free buffer zone. The waterborne polyurethane flexible carbon-free buffer zone is composed of the waterborne polyurethane fiber-bonded sealing layer that is not covered by the carbon-containing dissipation pattern and the polyhydroxyalkanoate / waterborne polyurethane carbon-free fiber-bonded pattern, and extends continuously along the cutting edge extension direction.
[0021] The polyhydroxyalkanoate / waterborne polyurethane carbon-free terminal corridor includes a polyhydroxyalkanoate / waterborne polyurethane layer formed on the waterborne polyurethane fiber sealing substrate and extends continuously along the cutting edge extension direction. The projections of the polyhydroxyalkanoate / waterborne polyurethane carbon-free terminal corridors located on the first main surface and the second main surface intersect on the porous fiber paper substrate to form a common projection area, and the final cut edge of the finished product is located within the common projection area.
[0022] In one periodic implementation, the cross-face phase-shifted functional mapping transition region extends periodically along the tangential extension direction and includes a first set of cross-face corresponding structures and a second set of cross-face corresponding structures. The first set of cross-face corresponding structures consists of a carbon-containing dissipation pattern on the first main surface and a polyhydroxyalkanoate / waterborne polyurethane carbon-free fiber-fixed pattern on the second main surface. The second set of cross-face corresponding structures consists of a carbon-containing dissipation pattern on the second main surface and a polyhydroxyalkanoate / waterborne polyurethane carbon-free fiber-fixed pattern on the first main surface. The first and second sets of cross-face corresponding structures have the same pattern period and are phase-shifted along the tangential extension direction, and are formed as periodic functional units or as non-collinear periodic paths. Within each pattern period, a double-sided common carbon-free interval is maintained between the first and second sets of cross-face corresponding structures, the double-sided common carbon-free interval corresponding to a region on both the first and second main surfaces that does not contain conductive carbon black.
[0023] In a further defined embodiment, after transforming the final dry patterns of the first main surface and the second main surface to a common finished product coordinate system and projecting them onto the mid-surface of the porous fiber paper substrate, the carbon-containing dissipative patterns on the first main surface and the second main surface have a carbon-containing projection overlap ratio ≤ 5%, the carbon-containing dissipative patterns on the first main surface have a first-direction cross-surface coverage ratio ≥ 95% relative to the polyhydroxyalkanoate / waterborne polyurethane carbon-free solid fiber patterns on the second main surface, and the carbon-containing dissipative patterns on the second main surface have a relative coverage ratio relative to the polyhydroxyalkanoate / waterborne polyurethane carbon-free solid fiber patterns on the first main surface. The second-direction cross-surface coverage ratio of the hydroxyl fatty acid ester / waterborne polyurethane carbon-free solid fiber pattern is ≥95%; the common projection area formed by the polyhydroxyl fatty acid ester / waterborne polyurethane carbon-free terminal corridor on the first main surface and the second main surface on the middle surface of the porous fiber paper substrate has a minimum width measured along the corridor width direction of ≥1.0mm; the shortest in-plane distance between the final cut edge of the finished product and the nearest area containing conductive carbon black on the first main surface, and the shortest in-plane distance between the final cut edge of the finished product and the nearest area containing conductive carbon black on the second main surface are both ≥4.5mm.
[0024] The carbon-containing projection overlap ratio can be 5%, 4.8%, 4.5%, 4.0%, 3.5%, 3.0%, 2.5%, 2.0%, 1.5%, 1.0%, 0.5%, or 0%. The first-direction cross-surface coverage ratio and the second-direction cross-surface coverage ratio can be 95%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98%, 98.5%, 99%, 99.5%, or 100%, respectively.
[0025] The minimum width of the common projection area measured along the width direction of the corridor is defined as the common projection width. The common projection width can be 1.0mm, 1.2mm, 1.5mm, 1.8mm, 2.0mm, 2.5mm, 3.0mm, 3.5mm, 4.0mm, 4.5mm, or 5.0mm.
[0026] The shortest in-plane distance from the final cut edge of the finished product to the nearest actual carbon-containing area on the first main surface is defined as the carbon-containing net distance on the first main surface, and the shortest in-plane distance from the final cut edge of the finished product to the nearest actual carbon-containing area on the second main surface is defined as the carbon-containing net distance on the second main surface. The carbon-containing net distances on the first and second main surfaces can be 4.5 mm, 4.8 mm, 5.0 mm, 5.5 mm, 6.0 mm, 6.5 mm, 7.0 mm, 7.5 mm, 8.0 mm, or greater than 8.0 mm.
[0027] In an embodiment that further tightens the cross-surface geometry, the carbon-containing projection overlap ratio is ≤3%, the cross-surface coverage ratio in the first direction and the cross-surface coverage ratio in the second direction are both ≥97%, the carbon-containing net distance between the first main surface and the carbon-containing net distance between the second main surface are both 5.5~8.0mm, and the common projection width is ≥2.0mm.
[0028] In one interdigitated embodiment, the cross-surface phase-shifting functional mapping transition region is an interdigitated cross-surface anti-overlapping transition region. The carbon-containing dissipation pattern located on the first main surface forms a first main surface carbon-containing dissipation functional unit, and the carbon-containing dissipation pattern located on the second main surface forms a second main surface carbon-containing dissipation functional unit; the PHA / WPU carbon-free fiber-fixing pattern located on the first main surface forms a first main surface PHA / WPU carbon-free fiber-fixing functional unit, and the PHA / WPU carbon-free fiber-fixing pattern located on the second main surface forms a second main surface PHA / WPU carbon-free fiber-fixing functional unit.
[0029] The carbon-containing dissipation functional unit on the first main surface and the carbon-free fiber-fixing functional unit on the second main surface form a first cross-face correspondence, and the carbon-containing dissipation functional unit on the second main surface and the carbon-free fiber-fixing functional unit on the first main surface form a second cross-face correspondence. The four types of functional units are arranged in the same pattern cycle along the tangential extension direction. The carbon-containing dissipation functional units on the two main surfaces are staggered along the tangential extension direction, and a common carbon-free interval is maintained on both main surfaces within each pattern cycle, where neither surface contains conductive carbon black.
[0030] In an embodiment that further defines the dimensions of the interdigitated structure, the width of the interdigitated cross-face reverse fitting transition zone along the width direction of the corridor is 3.5 to 5.0 mm, and can be 3.5 mm, 3.8 mm, 4.0 mm, 4.2 mm, 4.5 mm, 4.8 mm, or 5.0 mm.
[0031] The pattern period of the interdigitated cross-face reverse fitting transition zone is 4 to 6 mm, which can be 4.0 mm, 4.5 mm, 5.0 mm, 5.5 mm or 6.0 mm.
[0032] Within each pattern cycle, the lengths of the first main surface carbon dissipation functional unit and the second main surface carbon dissipation functional unit along the tangent extension direction are 20% to 40% of the pattern cycle, respectively, and can be 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38% or 40% of the pattern cycle.
[0033] The area coverage of the carbon-containing dissipation functional unit on each main surface within the interdigitated cross-surface anti-overlapping transition zone is 20% to 40%, which can be 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, or 40%. The sum of the nominal projected areas of the carbon-containing dissipation functional units on the two main surfaces is not greater than 80% of the area corresponding to the pattern period, thereby preserving the common carbon-free interval on both sides.
[0034] The length of the common carbon-free interval on both sides extending along the cutting edge is 20% to 60% of the pattern period, and can be 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55% or 60% of the pattern period.
[0035] In one embodiment, the carbon-containing dissipation functional units on the two main surfaces have equal lengths and are phase-staggered along the tangential extension direction. In other embodiments, the carbon-containing dissipation functional units on the two main surfaces may have different lengths or area coverage, as long as they are staggered and respectively form cross-face correspondences with the PHA / WPU carbon-free fiber-fixing functional units on the opposite main surfaces, and the common carbon-free interval on both sides is maintained in each pattern cycle.
[0036] In a dual-phase non-collinear path implementation, the cross-plane phase-shifting functional mapping transition region is a dual-phase non-collinear path transition region. A carbon-containing dissipation pattern located on the first master surface forms a first master surface carbon-containing dissipation path, and a carbon-containing dissipation pattern located on the second master surface forms a second master surface carbon-containing dissipation path. The first and second master surface carbon-containing dissipation paths are continuously connected to the electrostatic dissipation master regions of their respective master surfaces.
[0037] The PHA / WPU carbon-free fiber-bonding pattern located on the first main surface forms the PHA / WPU carbon-free fiber-bonding path on the first main surface, and the PHA / WPU carbon-free fiber-bonding pattern located on the second main surface forms the PHA / WPU carbon-free fiber-bonding path on the second main surface. The carbon-containing dissipation path on the first main surface and the PHA / WPU carbon-free fiber-bonding path on the second main surface form a first cross-plane corresponding path, and the carbon-containing dissipation path on the second main surface and the PHA / WPU carbon-free fiber-bonding path on the first main surface form a second cross-plane corresponding path.
[0038] The first and second cross-sectional corresponding paths extend periodically along the cutting edge extension direction and have a predetermined phase difference. After transforming the first and second cross-sectional corresponding paths to a common finished product coordinate system, their center lines do not coincide and are not located on the same straight line. The area between the first and second cross-sectional corresponding paths, as well as the side closest to the final cut edge of the finished product, is covered by a continuous carbon-free region.
[0039] In an embodiment that further limits the cross-surface coverage, the cross-surface coverage ratio of the carbon-containing dissipation path on the first main surface to the carbon-free fiber-fixing path on the second main surface is not less than 95%, and the cross-surface coverage ratio of the carbon-containing dissipation path on the second main surface to the carbon-free fiber-fixing path on the first main surface is not less than 95%.
[0040] The phase of each path group can be determined based on the starting point of the period of the carbon-containing dissipation path in that group. The pattern period, phase difference, path entity width, path centerline amplitude, and actual boundary clearance between the paths corresponding to the first and second cross-sections can be determined based on the transition zone width, double-sided registration accuracy, carbon-containing boundary expansion, and predetermined die-cutting deviation.
[0041] In a specific embodiment using PHBV, the width of the transition zone of the double-phase non-collinear path is 6.0 mm, the solid width of the first main surface PHBV / WPU carbon-free fiber-fixed path and the second main surface PHBV / WPU carbon-free fiber-fixed path are both 1.0 mm, the single-sided amplitude of the center line is 0.45 mm, and the pattern period is 6.0 mm. Taking the starting point of the period of the carbon-containing dissipation path in each group as the phase reference of the group, the phase difference between the first cross-face corresponding path and the second cross-face corresponding path is 50% of the pattern period. After projecting the first main surface PHBV / WPU carbon-free fiber-fixed path and the second main surface PHBV / WPU carbon-free fiber-fixed path onto the mid-surface of the porous fiber paper substrate, the shortest net distance between their actual boundaries is 1.2 mm.
[0042] The single-sided amplitude of the centerline refers to the maximum absolute offset of the path centerline relative to its periodic average centerline in the direction perpendicular to the periodic average centerline; the solid width refers to the actual dry boundary distance between the two sides measured along the local normal direction of the path centerline; the non-collinearity means that the centerlines of the first cross-plane corresponding path and the second cross-plane corresponding path do not coincide and are not located on the same straight line after being transformed to the common finished coordinate system.
[0043] In an embodiment that further tightens the final dry-state bifacial geometry, the carbon-containing projection overlap ratio is ≤3%, the cross-surface coverage ratio in the first direction and the cross-surface coverage ratio in the second direction are both ≥97%, the common projection width is ≥2.0mm, and the carbon-containing net distance between the first main surface and the second main surface is both 5.5~8.0mm. The double-phase non-collinear path structure can be tested and released as a finished product according to the same final dry-state bifacial geometry as the interdigitated cross-surface anti-overlay structure.
[0044] The WPU flexible carbon-free buffer zone is located between the cross-plane phase-shifting functional mapping transition zone and the PHA / WPU carbon-free terminal corridor. Its outermost surface is composed of a continuous WPU solid fiber sealing bottom layer. The carbon-containing dissipation pattern and the PHA / WPU carbon-free solid fiber pattern both terminate on the main area side of the WPU flexible carbon-free buffer zone.
[0045] The WPU flexible carbonless buffer zone serves two purposes: firstly, it absorbs positional errors caused by double-sided registration, carbon boundary expansion, paper swelling and shrinkage due to moisture, and die-cutting offset; secondly, it is located between the inner cross-plane phase-shifting functional mapping transition zone and the outer PHA / WPU carbonless terminal corridor, reducing the risk of two high solid load areas directly connecting to form a wide, hard ridge, and passivating cracks caused by damp heat or bending.
[0046] In some embodiments, the width of the WPU flexible carbon-free buffer zone along the width direction of the corridor is 1.5 to 3.0 mm, and can be 1.5 mm, 1.6 mm, 1.8 mm, 2.0 mm, 2.2 mm, 2.5 mm, 2.8 mm or 3.0 mm.
[0047] The PHA / WPU carbon-free terminal corridor is located on the cut edge side of the WPU flexible carbon-free buffer zone and continuously covers the predetermined tangent line. After projecting the PHA / WPU carbon-free terminal corridors on the two main surfaces onto the mid-surface of the porous fiber paper substrate, the two form a common projection area, and the predetermined tangent line is located within the common projection area.
[0048] In some embodiments, the finished product retention width of the PHA / WPU carbon-free terminal corridor, measured along the width direction of the corridor, is 3 to 5 mm, and can be 3.0 mm, 3.2 mm, 3.5 mm, 3.8 mm, 4.0 mm, 4.2 mm, 4.5 mm, 4.8 mm, or 5.0 mm.
[0049] In an embodiment that further limits the overlap of the terminal corridors of the two main surfaces, the common projection width of the PHA / WPU carbon-free terminal corridors of the two main surfaces at the final cut edge of the finished product is ≥1.0mm, and can be 1.0mm, 1.2mm, 1.5mm, 1.8mm, 2.0mm, 2.5mm, 3.0mm, 3.5mm, 4.0mm, 4.5mm or 5.0mm.
[0050] In some embodiments, the total width of the decoupling corridor along the width direction of the corridor is 8 to 13 mm, and can be 8.0 mm, 8.5 mm, 9.0 mm, 9.5 mm, 10.0 mm, 10.5 mm, 11.0 mm, 11.5 mm, 12.0 mm, 12.5 mm or 13.0 mm.
[0051] In an embodiment that further defines the spatial relationship between the final cut edge and the carbon-containing area, the shortest in-plane distance from the final cut edge of the finished product to any actual carbon-containing area is ≥4.5mm, which can be 4.5mm, 4.8mm, 5.0mm, 5.5mm, 6.0mm, 6.5mm, 7.0mm, 7.5mm, 8.0mm or greater than 8.0mm.
[0052] The shortest in-plane distance from the final cut edge of the finished product to any actual carbon-containing area can be further limited to 5.5–8.0 mm. Experimental results show that when the net distance increases from 3.0 mm to 4.5 mm, the risk of carbon exposure on the cut surface caused by the expansion of the carbon-containing boundary and die-cutting offset decreases; when the net distance continues to increase to 5.5–8.0 mm, the manufacturing tolerance further increases, but the occupation of the carbon-free area and the layout loss of small-sized products increase accordingly.
[0053] In some embodiments employing PHBV, the PHA in the PHA / WPU carbon-free fiber-fixing functional unit and the PHA / WPU carbon-free terminal corridor is PHBV. Based on the total polymer solids mass of PHBV and WPU, the PHBV content in the PHBV / WPU carbon-free fiber-fixing functional unit and the PHBV / WPU carbon-free terminal corridor is 20wt% to 35wt%, which can be 20wt%, 22wt%, 25wt%, 28wt%, 30wt%, 32wt%, or 35wt%, with the balance being WPU.
[0054] At lower PHBV contents, the cycling stability and coating flexibility of PHBV / WPU ink are more easily maintained, but edge hydrophobicity retention after damp heat may decrease; at higher PHBV contents, terminal fiber fixation and damp heat retention may be enhanced, but coating rigidity, particle agglomeration, plate clogging, and the risk of bending cracks may increase. Examples validated PHBV contents of 20 wt%, 28 wt%, and 35 wt%, where 20 wt% and 35 wt% correspond to the lower and upper ends of the range, respectively.
[0055] In some embodiments, the conductive carbon black content in the main electrostatic dissipation region and the carbon-containing dissipation pattern is 7wt% to 11wt% based on the total mass of the conductive carbon black and WPU functional solids, and can be 7wt%, 7.5wt%, 8wt%, 8.5wt%, 9wt%, 9.5wt%, 10wt%, 10.5wt%, or 11wt%, with the balance being WPU.
[0056] The conductive carbon black content should be determined based on the percolation threshold of the specific grade in the WPU system. Lower conductive carbon black content may reduce black transfer and frictional dusting, but may worsen low-humidity resistivity and post-aging resistivity stability; higher conductive carbon black content may improve electrostatic dissipation stability, but may increase the risk of black transfer, viscosity, boundary expansion, and dusting. Examples validated conductive carbon black contents of 7 wt%, 9 wt%, and 11 wt%, where 7 wt% and 11 wt% correspond to the lower and upper ends of the range, respectively.
[0057] As a further construction parameter, in some embodiments, the single-sided dry coating amount of the WPU fiber-bonded sealing substrate is 0.8–2.0 g / m². 2 It can be 0.8g / m 2 1.0g / m 2 1.2g / m 2 1.5g / m 2 1.8g / m 2 Or 2.0g / m 2 .
[0058] In some embodiments, the single-sided dry coating weight of the electrostatic dissipation main region is 2.0–3.0 g / m². 2 It can be 2.0g / m 2 2.2g / m 2 2.5g / m 2 2.8g / m 2 Or 3.0g / m 2 .
[0059] In some embodiments employing PHBV, the dry coating amount of the printed area of the PHBV / WPU carbon-free fiber-fixing functional unit and the PHBV / WPU carbon-free terminal corridor is 1.5–3.0 g / m², respectively. 2 It can be 1.5g / m 2 1.8g / m 2 2.0g / m 2 2.2g / m 2 2.5g / m 2 2.8g / m 2 Or 3.0g / m 2 .
[0060] The PHBV content, the conductive carbon black content, and the dry coating amount of the WPU fiber-bonding sealing underlayer, the electrostatic dissipation main area, and the PHBV / WPU printed area are used to adjust the terminal fiber bonding, electrostatic dissipation, coverage integrity, and mechanical stability, respectively. These parameters can be determined separately based on the corresponding performance characteristics; it is not required that the entire composition range and the entire dry coating amount range be limited as an indivisible fixed combination.
[0061] The basis weight of the porous fiber paper substrate is 70–110 g / m³. 2 It can be 70g / m 2 75g / m 2 80g / m 2 85g / m 2 90g / m 2 95g / m 2 100g / m 2 105g / m 2 Or 110g / m 2 .
[0062] After the electrostatic dissipation main region was conditioned for ≥48 hours at 23±2℃ and 12%±3% relative humidity and 23±2℃ and 50%±5% relative humidity respectively, the surface resistance was 10 Ω·cm. 5 ~10 9 Ω. The test electrode is fully positioned within the main electrostatic dissipation region and separated from the cross-plane phase-shifting functional mapping transition region, the WPU flexible carbon-free buffer zone, and the PHA / WPU carbon-free terminal corridor.
[0063] The present invention also provides a method for preparing the packaging material. The method includes: pretreating a porous fiber paper substrate to form a continuous WPU solid fiber sealing underlayer on a first main surface and a second main surface, respectively; using carbon-containing dissipative ink and PHA / WPU carbon-free solid fiber ink to form electrostatic dissipation main areas and decoupling corridors on the two main surfaces sequentially or simultaneously; drying the porous fiber paper substrate with the functional areas formed; and die-cutting or slitting within the common projection area formed by the PHA / WPU carbon-free terminal corridors on the two main surfaces to form the final trimmed edge of the finished product.
[0064] When forming the cross-surface phase-shifting functional mapping transition zone, the carbon-containing dissipation patterns located on the first main surface and the second main surface are misaligned along the tangent extension direction, so that the carbon-containing dissipation pattern located on the first main surface and the PHA / WPU carbon-free solid fiber pattern located on the second main surface form a cross-surface correspondence, and the carbon-containing dissipation pattern located on the second main surface and the PHA / WPU carbon-free solid fiber pattern located on the first main surface form a cross-surface correspondence.
[0065] The carbon-containing dissipation patterns are continuously connected to the electrostatic dissipation main areas of their respective main surfaces. Neither the carbon-containing dissipation patterns nor the PHA / WPU carbon-free fiber-bonded patterns extend into the WPU flexible carbon-free buffer zone. The WPU flexible carbon-free buffer zone is composed of a WPU fiber-bonded sealing layer not covered by the carbon-containing dissipation ink and the PHA / WPU carbon-free fiber-bonded ink. The PHA / WPU carbon-free terminal corridor is formed on the cut edge side of the WPU flexible carbon-free buffer zone, and the PHA / WPU carbon-free terminal corridors on the two main surfaces form a common projection area.
[0066] In the fabrication method using periodic patterns, a first set of cross-face corresponding structures and a second set of cross-face corresponding structures can be formed, with the two sets of cross-face corresponding structures arranged according to the same pattern period and staggered in phase along the tangent extension direction. The two sets of cross-face corresponding structures can be in the form of periodic functional units or non-collinear periodic paths. Within each pattern period, a common carbon-free space can be maintained on both sides between the first set of cross-face corresponding structures and the second set of cross-face corresponding structures.
[0067] In one preparation method, the WPU in the WPU solid fiber sealing bottom layer, the carbon-containing dissipative ink, and the PHA / WPU carbon-free solid fiber ink is obtained by splitting the same WPU master dispersion to improve the material compatibility between different functional regions.
[0068] In a preparation method that prevents cross-contamination, the carbon-containing dissipative ink and the PHA / WPU carbon-free solid fiber ink are transported using independent storage devices, pumping devices, circulation pipelines, filtration devices, and cleaning circuits to reduce the risk of conductive carbon black entering the carbon-free solid fiber pattern, the WPU flexible carbon-free buffer zone, and the PHA / WPU carbon-free terminal corridor.
[0069] In some embodiments, the functional ink wet layers on the two main surfaces undergo intermediate dehydration before entering a common final drying stage. Based on the measured temperature of the porous fiber paper substrate, the actual maximum temperature of the paper substrate during the common final drying stage is controlled to be 70–85°C, for example, 70°C, 72°C, 75°C, 78°C, 80°C, 82°C, or 85°C. In embodiments employing appropriate materials and drying conditions, the WPU forms a continuous film-forming phase, and the PHA forms a dispersed phase or phase-separated domain fixed by the continuous film-forming phase.
[0070] In the embodiment employing final dry state double-sided machine vision inspection, the final dry state patterns of the first main surface and the second main surface are acquired respectively. The final dry state patterns of the two main surfaces are transformed into a common finished product coordinate system and projected onto the mid-surface of the porous fiber paper substrate. The degree of overlap of the carbon-containing projections of the two main surfaces, the degree of cross-surface coverage in two directions, the continuity of the WPU flexible carbon-free buffer zone, the continuity of the PHA / WPU carbon-free terminal corridor, the common projection width, and the shortest distance from the predetermined tangent to the actual carbon-containing area of the two main surfaces are detected.
[0071] In a further embodiment employing quantitative die-cutting release, a porous fiber paper substrate is selected with a carbon projection overlap ratio ≤ 5%, a first-direction cross-surface coverage ratio and a second-direction cross-surface coverage ratio both ≥ 95%, a common projection width ≥ 1.0 mm, and a shortest in-plane distance ≥ 4.5 mm from the predetermined tangent to the nearest actual carbon-containing area on both the first and second main surfaces. Die-cutting or slitting is performed along the predetermined tangent within the common projection area, so that the predetermined tangent forms the final cut edge of the finished product.
[0072] The mirror correction of the second main surface image, the conversion of the two main surface images to a common finished product coordinate system, the calculation of the carbon-containing projection overlap ratio and the cross-surface coverage ratio in two directions, the value of the common projection width, and the calculation of the predetermined tangent carbon-containing net distance can be implemented according to the double-sided cross-surface projection relationship determination method described in this specification.
[0073] The present invention also provides a packaging system for clean isolation of semiconductors and electronic components. The packaging system includes the aforementioned packaging material, a conductive turnover container, a conductive contact portion, and a grounding connector. The packaging material is disposed within the conductive turnover container; the conductive contact portion is disposed on the side of the packaging material facing the conductive turnover container and located within the main electrostatic dissipation region, the main electrostatic dissipation region being conductively connected to the conductive turnover container via the conductive contact portion; the conductive turnover container is connected to a common grounding point via the grounding connector, and the main electrostatic dissipation region, the conductive contact portion, the conductive turnover container, and the grounding connector form a system grounding path connected to the common grounding point.
[0074] The present invention also provides the application of the packaging system in the storage, transportation, inter-process handling or cleanroom isolation of semiconductor devices or electronic components.
[0075] In some embodiments, the conductive turnover container is a reusable conductive turnover container. The packaging material is used in the form of a liner, spacer, divider, or sleeve disposed inside the conductive turnover container and located between the packaged object and the conductive turnover container.
[0076] In some embodiments, the packaging system further includes a carrier for carrying the semiconductor device or electronic component. The carrier includes one of a tray, a feed tube, a carrier belt, or a container.
[0077] In some embodiments, the semiconductor device or electronic component is one or more of a packaged and non-powered integrated circuit, sensor, connector, printed circuit board module, or electronic assembly.
[0078] In some embodiments, the carrier spacers the packaging material from the sensitive surface of the semiconductor device or electronic component. The sensitive surface includes a microelectromechanical system (MEMS) sensitive surface, a critical optical surface, or an exposed gold finger.
[0079] The conductive turnover container provides a system grounding connection. The electrostatic dissipation main region of the packaging material forms a local in-plane charge dissipation path. The waterborne polyurethane flexible carbon-free buffer zone, the polyhydroxyalkanoate / waterborne polyurethane carbon-free terminal corridor, and the finished product's final cut edge form a clean isolation structure near the edge of the packaging material. The conductive contact portion is located within the electrostatic dissipation main region and is spatially separated from the waterborne polyurethane flexible carbon-free buffer zone, the polyhydroxyalkanoate / waterborne polyurethane carbon-free terminal corridor, and the finished product's final cut edge.
[0080] Compared with the prior art, the present invention has the following beneficial effects:
[0081] This invention sets misaligned carbon-containing dissipation patterns in the cross-plane phase-mapped transition zone between two main surfaces, and makes the carbon-containing dissipation pattern on one main surface correspond to the PHA / WPU carbon-free solid fiber pattern on the opposite main surface. This reduces the degree of overlap of the carbon-containing areas on the two main surfaces at the same thickness position, and reduces the risk of local rigid superposition, friction powdering, and bending cracking of the carbon-containing areas on both sides.
[0082] In the implementation using periodic patterns, a first set of cross-face corresponding structures and a second set of cross-face corresponding structures are provided in the cross-face phase-shifted functional mapping transition region. The first set of cross-face corresponding structures forms a cross-face correspondence between the carbon-containing dissipation pattern on the first main surface and the PHA / WPU carbon-free fiber-fixed pattern on the second main surface. The second set of cross-face corresponding structures forms a cross-face correspondence between the carbon-containing dissipation pattern on the second main surface and the PHA / WPU carbon-free fiber-fixed pattern on the first main surface. Both sets of cross-face corresponding structures use the same pattern period but are phase-shifted, maintaining a common carbon-free interval on both sides within each pattern period.
[0083] In an embodiment that further defines the final dry-state biplane geometric relationship, the carbon-containing projection overlap ratio is no higher than 5%, and the cross-plane coverage ratio in the first direction and the cross-plane coverage ratio in the second direction are both no less than 95%. The interdigitated cross-plane anti-register structure can form the above-mentioned cross-plane corresponding relationship through periodic functional units, and the double-phase non-collinear path structure can form the above-mentioned cross-plane corresponding relationship through non-collinear and phase-staggered periodic paths.
[0084] This invention connects all carbon-containing dissipation patterns continuously with the same-plane electrostatic dissipation main region, with its outer boundary located inside the main region side boundary of the WPU flexible carbon-free buffer zone, so that the area near the final cut edge is covered by a continuous carbon-free structure.
[0085] The WPU flexible carbon-free buffer zone is located between the cross-plane phase-shifting functional mapping zone and the PHA / WPU terminal corridor. It absorbs manufacturing position deviations and passivates cracks without adding a third type of resin, and reduces the direct connection of PHA-enriched areas to form a wide hard ridge.
[0086] The PHA / WPU carbon-free terminal corridor forms a common projection area at the final cut edges of the two main surfaces, so that the die-cut line is located in the carbon-free fiber-fixed area on both surfaces, which helps to reduce carbon black hot spots, black transfer, paper fiber particles and coating particles released from the cut surface.
[0087] In the embodiment where the WPU forms the fiber-sealing bottom layer, the carbon-containing dissipation pattern, and the carbon-free region of the PHA / WPU, and the PHA forms a dispersed phase or phase separation domain fixed by the WPU, the interfacial incompatibility between different functional regions can be reduced, and the PHA can play a role in moisture and heat edge retention and local fiber fixation at a lower paper web temperature.
[0088] The double-sided functional structure of the present invention can be formed by water-based coating or printing, and can be integrated with hot air drying, infrared drying, rotary die-cutting and vacuum dust removal equipment, which is beneficial for continuous production and large-scale production.
[0089] In the implementation of final dry double-sided machine vision inspection and quantitative die-cutting release, the die-cutting or slitting position can be determined based on the actual dry pattern rather than just the nominal printing plate pattern, so that a traceable quality control closed loop is formed between the nominal pattern, the actual dry pattern, the inspection results and the final cut edge of the finished product. Attached Figure Description
[0090] Figure 1 This is a schematic diagram illustrating the structural mechanism and system application of PHA bio-based antistatic low-dust barrier packaging material with an interdigitated cross-face reverse fitting structure for clean isolation of semiconductors and electronic components.
[0091] In the diagram: 1-Porous fiber paper substrate; 2-Waterborne polyurethane fiber-sealing bottom layer; 3-Electrostatic dissipation main area; 4-Interdigitated cross-face reverse-fit transition area; 5-Carbon-containing dissipation functional unit; 6-PHBV / waterborne polyurethane carbon-free fiber-sealing functional unit; 7-Double-sided common carbon-free spacer; 8-Waterborne polyurethane flexible carbon-free buffer zone; 9-PHBV / waterborne polyurethane carbon-free terminal corridor; 10-Final trimming of finished product; 11-System grounding path; 12-Clean isolation area. Detailed Implementation
[0092] The technical solution of the present invention will be further described below with reference to the accompanying drawings, embodiments, and comparative examples. Unless otherwise stated, the raw materials used are commercially available industrial products or prepared according to the methods described herein, and performance tests are performed according to the following methods.
[0093] Figure 1This diagram illustrates one embodiment of an interdigitated cross-face reverse alignment structure. A porous fiber paper substrate 1 serves as the supporting framework, with continuous waterborne polyurethane fiber-sealed bottom layer 2 and electrostatic dissipation main area 3 respectively disposed on its two main surfaces. The electrostatic dissipation main area 3, facing the final cut edge 10 of the finished product, is connected to an interdigitated cross-face reverse alignment transition area 4. The carbon-containing dissipation functional units 5 on the two main surfaces are phase-shifted along a direction parallel to the final cut edge 10 of the finished product, and form a cross-face correspondence with the PHBV / waterborne polyurethane carbon-free fiber-sealed functional unit 6 on the opposite surface, thereby reducing the overlap of the carbon-containing areas on both sides in the thickness direction and forming a common carbon-free interval 7 on both sides. A waterborne polyurethane flexible carbon-free buffer zone 8 and a PHBV / waterborne polyurethane carbon-free terminal corridor 9 are sequentially disposed outside the interdigitated cross-face reverse alignment transition area 4, so that the final cut edge 10 of the finished product is located within the common projection area of the carbon-free terminal corridors of the two main surfaces. The electrostatic dissipation main area 3 forms a conductive connection with the conductive turnover container through the conductive contact part. The conductive turnover container is connected to the common grounding point through the grounding connector, thereby forming a system grounding path 11. The waterborne polyurethane flexible carbon-free buffer zone 8, the PHBV / waterborne polyurethane carbon-free terminal corridor 9 and the final cut edge of the finished product 10 together form a clean isolation area 12.
[0094] The main reagents and raw materials are shown in Table 1.
[0095] Table 1. Main reagents and raw materials.
[0096]
[0097] Except for Example 9, which used the aliphatic WPU sample PUR-MATT 310, Examples 1-8, 10, 11, and Comparative Examples 1-12 all used Bayhydrol UH 2889. The solid fiber sealing substrate, carbon-containing dissipative ink, and PHBV / WPU carbon-free solid fiber ink in the same example or comparative example were all prepared from the same batch of WPU master dispersion to maintain the consistency of the continuous film-forming phase.
[0098] Preparation of PHBV micro powder PV3000G-M10.
[0099] Step 1: Place the PV3000G resin in a vacuum drying oven at 40°C and an absolute pressure not exceeding 5 kPa for 12 hours. After drying, place it in a desiccator to cool to room temperature.
[0100] Step 2: Weigh 100.0g of dried PV3000G resin, add it to a low-temperature pulverizing tank, and purge it with liquid nitrogen to lower the resin temperature to below -80℃ for 10 minutes.
[0101] Step 3: Use a low-temperature vibrating ball mill to grind at a frequency of 25 Hz for 2 minutes, stop for 1 minute, and repeat the grinding process twice. During the grinding process, continuously replenish liquid nitrogen to keep the material temperature below -60℃.
[0102] Step 4: Pass the pulverized material through a 20μm sieve and collect the material that passes through the sieve; repeat the same low-temperature pulverization process on the material that passes through the sieve.
[0103] Step 5: Add all the sieved material to the ATP 20 classification module of the Hosokawa Alpine Picoline Picosplit ultrafine airflow classifier for particle size classification. The classification equipment and all collection containers are electrically grounded. Dry compressed air with a dew point not exceeding −20°C is used as the classification gas. The classifying wheel speed is controlled at 40,000–50,000 rpm, and the total gas volume is controlled at 10–14 Nm³. 3 The feed rate is controlled at 1.5–2.5 g / min per hour, and fine powder and coarse powder are collected separately.
[0104] The D of the obtained fine powder was determined according to ISO 13320:2020. 10 D 50 and D 90 When the fine powder D 90 When the particle size is greater than 10 μm, the fine powder is subjected to a classifier rotation speed of 50,000–55,000 rpm and a total air volume of 10–12 Nm³. 3 Under the condition of / h, classify again. Only collect D. 90 Fine powder with a particle size of no more than 10 μm is used as PV3000G-M10 micro powder, while coarse powder is returned to step 3 for the same low-temperature pulverization and reclassification.
[0105] Step 6: Determine the particle size distribution according to ISO 13320:2020. The particle sizes corresponding to cumulative volume distribution reaching 10%, 50%, and 90% are denoted as D. 10 D 50 and D 90 Qualified batch D 10 1–3 μm, D 50 3–6 μm, D 90 No larger than 10μm.
[0106] Step 7: Place the qualified PHBV micro powder in an aluminum-plastic composite bag, seal it with nitrogen, and store it at 5±2℃. Use it within 30 days.
[0107] Main analytical and testing instruments.
[0108] Table 2. Main analytical and testing instruments.
[0109]
[0110] Main testing standards:
[0111] Table 3. Main test standards.
[0112]
[0113] Test method:
[0114] Unless otherwise specified, all tests were conducted using three independently prepared production batches. Each batch underwent independent weighing, ink preparation, coating or printing, drying, die-cutting, dust removal, and sampling. Six finished product samples were randomly selected from each batch, for a total of 18 samples tested, denoted as n = 18. Except for surface resistivity, the continuous results in Tables 4 to 10 are expressed as the arithmetic mean ± sample standard deviation of the 18 samples, with the denominator of the sample standard deviation being n−1; surface resistivity was processed according to the following geometrical statistical methods.
[0115] Surface resistivity is first calculated by taking the logarithm to base 10 of a single measurement, then the arithmetic mean and sample standard deviation of the logarithms are calculated; the results are expressed as geometric mean and geometric standard deviation. Geometric mean = 10 Σlog10(Ri) / n Geometric standard deviation (GSD) = 10 SD[log10(Ri)] Resistance drift is calculated as the absolute value of the base-10 logarithm of the ratio of the geometric mean of surface resistance before and after treatment.
[0116] The original cumulative particle count output by the particle counter for each sampling period is rounded to the nearest integer. The particle release per unit cut edge length for each sample is calculated based on the difference between the average of the original cumulative particle counts from 5 formal samplings and the average of the original cumulative particle counts from 5 blank samplings; the individual sample calculation result is not pre-rounded. The group average and sample standard deviation are calculated using the individual results from 18 samples without pre-rounding, and rounded to 1·m. -1 Hot spots on the cross-section of carbon black are counted as whole numbers per piece. All values after "±" in the table represent the sample standard deviation, except for the geometric standard deviation.
[0117] Tables 4 to 6 list the continuous measurement results under different application conditions, without classification criteria. Table 7 lists the results for particles no larger than 1300 particles per cubic meter. -1 Black transfer ΔL * Not greater than 2.50, and the total crack length not greater than 18 mm·m -1 The delamination area is no more than 2.0% and the surface resistivity is within 10. 5 ~10 9 Ω is used as a preset composite evaluation condition. The composite evaluation in Table 7 is only used for cross-sectional comparison of different samples under the same experimental conditions. The technical effect is analyzed by combining the continuous measured results and their statistical values.
[0118] Performance testing of construction fluid and PHBV micro powder.
[0119] According to ISO 3251:2019, the non-volatile content of WPU master dispersion, WPU solid fiber sealing primer, carbon-containing dissipative ink, PHBV / WPU carbon-free solid fiber ink and WPU carbon-free control ink were determined respectively. The actual amount of WPU in all formulations was converted according to the measured non-volatile content of the corresponding batch.
[0120] According to ISO 976:2013, the pH of the functional ink was determined after preparation, after 4 hours of circulation, and after 8 hours of circulation at 23±2℃; according to ISO 2555:2018, the apparent viscosity was determined at the corresponding time points using the same rotor and rotation speed at 25±0.5℃.
[0121] The D of dispersed particles in PHBV micro powder and PHBV / WPU carbon-free solid fiber ink was determined according to ISO 13320:2020. 10 D 50 and D 90 The dispersion medium, refractive index parameters, pre-dispersion conditions, and particle size changes before and after cycling were recorded.
[0122] Measurement of surface resistance in the main region of electrostatic dissipation.
[0123] The surface resistance measurement procedure was performed according to IEC 61340-2-3:2016 / COR1:2023, using a Keithley 6517B high-resistivity meter and a Keithley 8009 concentric ring electrode fixture. The formal test voltage was determined based on the resistance level obtained from the preliminary test: the resistance should not be less than 1 × 10⁻⁶. 6 When the resistance is Ω, the test voltage is 100±5V; when the resistance is less than 1×10 6 When the Ω is Ω, the test voltage is 10.0±0.5V.
[0124] The electrode is fully positioned within the main electrostatic dissipation region, with its outer edge extending at least 10 mm from the transition zone of the cross-plane phase-shifting function, and does not cross the WPU flexible carbon-free buffer zone or the PHBV / WPU carbon-free terminal corridor. The concentric ring electrode does not differentiate between machine orientation and lateral direction.
[0125] After placing the electrode, let it stand for 10 seconds, then apply the test voltage and read the surface resistance after 60 seconds. If it is still not stable after 60 seconds, continue to 120 seconds and record the values at 60 seconds and 120 seconds at the same time. The range determination in this manual adopts the value at 60 seconds.
[0126] The measurement procedure was performed according to the aforementioned standard. The samples were conditioned for no less than 48 hours in environments of 23±2℃ and 12%±3% relative humidity and 23±2℃ and 50%±5% relative humidity, respectively. Different finished samples were used for low humidity and medium humidity tests. Five non-overlapping positions were measured on the first and second main surfaces of each sample, and 90 single measurements were obtained for each main surface.
[0127] Determination of the relationship between two-sided cross-plane projections.
[0128] With the final cut edge centerline of the finished product as the x=0 reference, the direction perpendicular to the final cut edge and pointing towards the main electrostatic dissipation region is the positive x-axis, and the direction parallel to the final cut edge and extending along the pattern period is the positive y-axis. The start and end coordinates of the carbon-containing region are based on the final dry carbon-containing boundary confirmed by micro Raman spectroscopy.
[0129] Online inspection employed a KEYENCE XG-X2802 duplex machine vision controller and two CA-HL08MX line scan cameras. The two cameras respectively acquired the final dry-state patterns of the first and second main surfaces. With a 300mm lateral field of view, the nominal lateral sampling interval was 0.0375mm / pixel. Offline inspection used a KEYENCE VHX-X1 digital microscope to verify the carbon-containing boundaries, carbon-free fiber-fixed pattern boundaries, and terminal corridor boundaries.
[0130] The second master surface image is mirrored and corrected. An affine transformation is established using at least three non-collinear registration marks or corresponding geometric reference points to convert the two patterns to a common finished product coordinate system. After the affine transformation, the planar residual of each reference point is no greater than 0.05 mm, and the maximum difference in the carbon-containing boundary coordinates obtained by repeatedly acquiring the same area three times is no greater than 0.10 mm.
[0131] The final dry patterns on both sides are projected onto the middle surface of the paper base, and the carbon-containing projection overlap ratio, the cross-surface coverage ratio in both directions, the common projection width of the terminal corridor, and the actual carbon-containing net distance between the two sides are calculated respectively.
[0132] Let C1 be the carbon-containing region mask on the first main surface, C2 be the carbon-containing region mask on the second main surface, P1 be the PHA region mask on the first main surface, and P2 be the PHA region mask on the second main surface. The PHA regions of the samples measured below are all PHBV regions.
[0133] For the interdigitated cross-surface inverse registration structure, C1 and C2 are carbon-containing dissipation functional unit masks for the two main surfaces, and P1 and P2 are PHA / WPU carbon-free fiber-bonded functional unit masks for the two main surfaces. For the double-phase non-collinear path structure, C1 and C2 are carbon-containing dissipation path masks for the two main surfaces, and P1 and P2 are PHA / WPU carbon-free fiber-bonded path masks for the two main surfaces. The carbon projection overlap ratio and the cross-surface coverage ratio in both directions for the two structures are calculated using the following formulas.
[0134] The carbon-containing projective overlap ratio is calculated using the following formula:
[0135] Carbon projection overlap ratio = area (C1∩C2) ÷ min [area (C1), area (C2)] × 100%.
[0136] The coverage ratio of the carbon-containing region on the first primary surface to the PHA region on the second primary surface is calculated using the following formula:
[0137] First direction cross-surface coverage ratio = area (C1∩P2) ÷ area (C1) × 100%.
[0138] The coverage ratio of the carbon-containing region on the second main surface to the PHA region on the first main surface is calculated using the following formula:
[0139] Second direction cross-surface coverage ratio = area (C2∩P1) ÷ area (C2) × 100%.
[0140] Online vision is used for continuous inspection, while offline microscopic Raman spectroscopy is used to confirm the carbon black area, and microscopic infrared spectroscopy or microscopic Raman spectroscopy is used to confirm the PHA area.
[0141] Determination of carbon-containing and carbon-free areas:
[0142] In this specification, "carbon-containing" means that conductive carbon black is actively added to the corresponding construction liquid, pattern, or area; "carbon-free" means that conductive carbon black is not actively added to the corresponding construction liquid, and the final dry area does not show conductive carbon black D and G bands exceeding the judgment threshold by the following micro Raman spectroscopy. This does not mean that it does not contain carbon elements formed by paper fibers, PHA, or WPU.
[0143] Within the WPU flexible carbon-free buffer zone and the PHA / WPU carbon-free terminal corridor, a grid scan was performed with a 1mm × 1mm detection window. The detection location was approximately 1350cm. -1 D-band and approximately 1580cm -1 If none of the integrated signals of the G-band exceed the average signal of the blank WPU / PHA without conductive carbon black plus 3 times the standard deviation, it is determined that no conductive carbon black is detected in the detection window; if any integrated signal exceeds the corresponding judgment threshold, it is determined that conductive carbon black is detected.
[0144] When it is necessary to report the mass fraction of locally conductive carbon black, a calibration curve is established using WPU standard dry films with conductive carbon black mass fractions of 0 wt%, 0.1 wt%, 0.3 wt%, 0.5 wt%, and 1.0 wt%.
[0145] Final measurement of the net distance from the cut edge to the carbon-containing area:
[0146] Step 1: Extract the final cut centerline from the common coordinate image.
[0147] Step 2: Extract all actual carbon-containing region boundaries of the first and second main surfaces.
[0148] Step 3: Calculate the two-dimensional Euclidean shortest distance from the final cut edge centerline to the boundary of any actual carbon-containing region.
[0149] Step 4: Report the minimum values of the first and second main surfaces respectively, and use the smaller value between the two for finished product determination.
[0150] Measurement of the combined projection width of the double-sided terminal corridor.
[0151] Project the PHA / WPU carbonless terminal corridors of the first and second main surfaces onto a common coordinate system and calculate their intersection area.
[0152] The common projection width is measured every 1 mm along the direction perpendicular to the final cut edge. The minimum common projection width within the entire final cut edge range is taken as the result.
[0153] Measurement of particle release per unit cut edge length:
[0154] An SM 30 B control horizontal reciprocating oscillator manufactured by Edmund Bühler GmbH was used, and the oscillator was placed within a closed test space formed by a Terra Universal 1993-95E electrostatic dissipation PVC transfer window. Both side doors were closed during the test. The internal dimensions of the closed test space were 914.4 mm × 914.4 mm × 1219.2 mm, with a geometric volume of 1.019 m³. 3 After deducting the outer envelope volume of the horizontal reciprocating oscillator (680mm × 610mm × 160mm), the effective net volume of the enclosed test space is approximately 0.953m³. 3 The volume occupied by the test specimen and the fastener will not be deducted separately.
[0155] A Solair 3100 optical particle counter was used to record particles with diameters of not less than 0.5 μm, 1 μm, 5 μm, and 10 μm using a cumulative counting method. The sampling flow rate was 28.3 L / min, the single sampling period was 60 s, the number of consecutive samples was 5, and the interval between adjacent sampling periods was 0 s; the sampling volume of a single sampling period was 0.0283 m³. 3 The total sampling volume for each sample across 5 sampling cycles was 0.1415 m³. 3 The sampling port is located 100 mm above the geometric center of the sample, and its position and orientation remain unchanged during the test.
[0156] Before each sample is formally tested, with the horizontal reciprocating oscillator, sample fixing parts and sampling port positions remaining unchanged and no sample placed, the two doors of the enclosed test space are closed, and five consecutive 60-second blank samplings are performed. The original cumulative particle counts for each particle size threshold in the five blank sampling cycles are recorded, and the arithmetic mean of the five blank samplings is used as the background particle count corresponding to that sample.
[0157] Cut a sample with 100mm of the final cut edge of the finished product to be tested, and seal the remaining cut edges. First, bend the sample 180° back and forth 10 times around a circular shaft with a radius of 2mm, and then vibrate it for 5 minutes at a stroke of 30mm and a frequency of 60 times / min.
[0158] After vibration ceases, allow the space to stand still for 10 seconds, keeping both doors of the enclosed test space closed. Immediately begin five consecutive 60-second formal sampling cycles, with a 0-second interval between adjacent formal sampling periods. The particle release per unit cut edge length for each particle size threshold is calculated using the following formula:
[0159] N=[(ΣN s,j / 5)−(ΣN b,j / 5)] / L, j=1, 2, 3, 4, 5.
[0160] In the formula, N represents the particle release per unit tangential length under specified sampling conditions, expressed in particles per m³. -1 N s,j N represents the raw cumulative particle count output by the particle counter during the j-th formal sampling period, expressed in units of particles; b,j is the raw cumulative particle count output by the particle counter in the j-th blank sampling period, in units of particles; L is the final cut edge length of the actual tested product, which is 0.100m in this experiment. If the calculated result after background subtraction is less than zero, it is counted as zero.
[0161] The particle release per unit cut length in this specification is an operational particle release index obtained under specified closed test space, sampling flow rate, sampling time, sampling location, mechanical excitation method, and actual test cut length. It is used for cross-sectional comparison of different packaging materials under the same test conditions and does not represent the total number of particles actually present in the closed test space.
[0162] Report the release of particles per unit tangential length with particle sizes of not less than 0.5 μm, 1 μm, 5 μm and 10 μm respectively. The comprehensive analysis of each application example uses the results of particles with a particle size of not less than 1 μm.
[0163] Particles were collected using a settling membrane, and paper fibers, WPU particles, PHBV / WPU particles, and carbon-containing particles were distinguished by micro-infrared, micro-Raman, and morphological observation.
[0164] Black transfer ΔL * Measurement:
[0165] A clean, white polyethylene terephthalate (PET) acceptor membrane with a thickness of 50±3 μm and no surface coating was used. The initial L of the acceptor membrane was measured using a CM-26dG spectrophotometer before rubbing. * The values are set under the following conditions: D65 standard light source, 10° standard observer, specular reflection inclusion mode, and 8mm measurement aperture.
[0166] Five fixed measurement points were set on each receptor membrane, with an initial L * The value was 96.8 ± 0.3. The receptor membrane was fixed to the friction head of a Sutherland friction testing machine and rubbed back and forth 50 times under a load of 9 N and a speed of 42 times / min.
[0167] After friction, L was measured again at the same five coordinate positions as the initial measurement. * The value of black transfer is calculated using the following formula: ΔL * =|L0−L1|.
[0168] In the formula, L0 is the L before friction at 5 measuring points. * The arithmetic mean of the values, L1 is the L after friction at the same 5 measuring points. * The arithmetic mean of the values. ΔL is calculated for each sample using 5 measuring points. * This is the result of the sample.
[0169] The electrostatic dissipation main region, the decoupling corridor, and the area near the final cut edge were tested separately, and the location of the black contamination was confirmed by micro Raman spectroscopy.
[0170] The results are expressed as the arithmetic mean and sample standard deviation of 18 samples.
[0171] Crack and delamination determination:
[0172] The KEYENCE VHX-X1 digital microscope was used to perform continuous stitching scans of the cross-plane phase-shifting functional mapping transition zone, the WPU flexible carbon-free buffer zone, and the PHBV / WPU carbon-free terminal corridor.
[0173] The entire region was imaged at 100x magnification, and crack endpoints, bifurcation, and delamination boundaries were identified at 500x magnification. Linear openings with a width of at least 2 μm and a projected length of at least 20 μm were defined as cracks.
[0174] The crack centerline length is calculated using an image skeletonization method; when the crack bifurcates, the length of each branch is calculated separately, while the common connection segment is calculated only once. The layered area ratio is the pixel area of the confirmed layered region divided by the total pixel area of the observed region.
[0175] Report the total length of cracks per unit corridor, the maximum length of a single crack, whether the crack crosses the WPU flexible carbon-free buffer zone, whether the crack reaches the final cut edge, the proportion of delamination area to the observed area, and the maximum delamination width.
[0176] The samples were treated at 40±2℃ and 90%±5% relative humidity for 168 hours, then restored at 23±2℃ and 50%±5% relative humidity for 24 hours before particle, crack, delamination, black transfer and resistance tests were performed.
[0177] Measurement of hot spots in cross-section carbon black:
[0178] Hot spots of carbon black on the cross-section were identified using a Renishaw inVia Qontor micro Raman spectroscopy system. The laser wavelength was 532 nm, the objective magnification was 50x, the laser power on the sample surface did not exceed 1 mW, the integration time was 1 s for each scan, and a total of 3 scans were performed. The scanning range was 800–2000 cm⁻¹. -1 .
[0179] When the detection location is approximately 1350cm -1 D-band and approximately 1580cm -1 When the G-band signal of a carbon black hotspot is found to be greater than the average signal of the blank section of the carbon-free WPU / PHBV and three times the standard deviation, it is considered a carbon black hotspot.
[0180] Scan along the final 100mm cut edge using a continuous field of view; signals belonging to the same continuous carbon black region in adjacent fields of view are combined into one hot spot, and the result is expressed as a unit (100mm). -1 express.
[0181] System point-to-ground resistance and charge decay measurement:
[0182] The classification of electrostatic protection properties of packaging materials and packaging systems is in accordance with IEC 61340-5-3:2022. Point-to-point resistance of the inner surface of the container, point-to-ground resistance of the container, and point-to-ground resistance of the main electrostatic dissipation area of the packaging material are measured in accordance with IEC 61340-2-3:2016 / COR1:2023.
[0183] Unless otherwise specified, the packaging material samples, conductive turnover containers, and assembled packaging systems were conditioned at 23±2℃ and 50%±5% relative humidity for at least 48 hours, and resistance measurements were performed under the same temperature and humidity conditions. A Keithley 6517B high-resistance meter and a weighted electrode assembly conforming to Clause 8.2.4 of IEC 61340-2-3:2016 / COR1:2023 were used. Each weighted electrode had a conductive rubber contact surface with a diameter of 63.5±1.0 mm, a total electrode mass of 2.5±0.25 kg, and a Shore A hardness of 50–70 for the conductive rubber.
[0184] When measuring the point-to-point resistance of the inner surface of the container, disconnect the grounding wire between the conductive container and the common grounding point, and place the conductive container on an insulating support surface with a surface resistance and volume resistivity of not less than 1×10¹³Ω. Place two weighted electrodes on a flat area of the bottom surface of the conductive container, with a distance of 250±5mm between the centers of the contact surfaces of the two electrodes, and maintain a distance of not less than 30mm between each electrode and the container edge, reinforcing ribs, and seams. Five sets of specified locations are selected for measurement for each conductive container, and one point-to-point resistance value is obtained for each set of locations.
[0185] When measuring the point-to-ground resistance of the container, the grounding terminal on the outside of the conductive container is connected to a common grounding point via a grounding wire connected in series with a 1MΩ safety resistor, as described in Application Example 6. A weighted electrode is placed on a flat area of the bottom surface inside the conductive container. One end of a high-resistance meter is connected to the weighted electrode, and the other end is connected to the common grounding point. Measurements are performed at five specified locations for each conductive container. The obtained point-to-ground resistance includes the resistance value of the 1MΩ safety resistor; the 1MΩ safety resistor is not subtracted from the measurement result.
[0186] When measuring the point-to-ground resistance of the main electrostatic dissipation zone of packaging materials, the packaging materials are placed inside a conductive container according to their actual usage. The main electrostatic dissipation zone is conductively connected to the conductive container through the conductive contact portion, and the conductive container is connected to the common grounding point through a grounding wire with a 1MΩ safety resistor in series. A weighted electrode is placed entirely within the main electrostatic dissipation zone, with the shortest distance from the outer edge of the weighted electrode's contact surface to the transition zone of the cross-plane phase-shifting functional mapping not less than 10mm. One end of the high-resistance meter is connected to the weighted electrode, and the other end is connected to the common grounding point. Five non-overlapping locations are measured within the main electrostatic dissipation zone for each piece of packaging material. The obtained point-to-ground resistance of the main electrostatic dissipation zone of the packaging material includes the actual system path formed by the conductive contact portion, the conductive container, the grounding connector, and the 1MΩ safety resistor; the 1MΩ safety resistor is not deducted from the measurement results.
[0187] The formal test voltage is determined based on the resistance level obtained from the preliminary test: resistance below 1×10⁻⁶. 6 When the resistance is Ω, a test voltage of 10.0±0.5V is used, and the resistance is not less than 1×10. 6 For resistances exceeding Ω, a test voltage of 100±5V is used. After placing the electrodes, allow them to rest for 10 seconds before applying the test voltage, and read the resistance value after 60 seconds of energization. Measurements exceeding 1×10⁻⁶... 12 When Ω, the report is >1×10 12 Ω.
[0188] For each sample, the point-to-point resistance of the container's inner surface, the point-to-ground resistance of the container, and the point-to-ground resistance of the main electrostatic dissipation area of the packaging material were calculated using the geometric mean of five measurements taken from each sample. The group results were expressed as the geometric mean and geometric standard deviation of the individual results from all 18 samples.
[0189] The continuity of the connection between the grounding connector, conductive clamp, and grounding terminal was determined using a Keithley DMM6500 digital multimeter in four-wire resistance mode. The measurement range included the conductive clamp, the metal grounding terminal of the conductive container, and the metal connection portion of the grounding connector located on the 1MΩ safety resistor container side, excluding the 1MΩ safety resistor itself. All groups used the same conductive clamping position, clamping pressure, and wiring method.
[0190] The charge decay test was conducted according to the charged metal plate method in IEC 61340-2-1:2015+AMD1:2022, and performed according to the following packaging system connection method. An Advanced Energy Trek 158A charged metal plate monitor and a 150mm × 150mm charged metal plate assembly were used. The charged metal plate was electrically connected to the main electrostatic dissipation area of the packaging material via conductive clamps. The main electrostatic dissipation area of the packaging material was connected to the common grounding point through the conductive contacts, the conductive turnover container, the grounding connector, and the 1MΩ safety resistor.
[0191] For the positive polarity test, the charged metal plate is charged to +1000V, and the time required for the potential to decay to +100V is recorded after the charging source is disconnected. For the negative polarity test, the charged metal plate is charged to -1000V, and the time required for the potential to decay to -100V is recorded after the charging source is disconnected. The residual potential at 2s is also recorded.
[0192] Each sample was subjected to charge decay tests with both positive and negative polarities, and V was taken. 2s =max(|V 2s,+ |,|V 2s,- |) is used as the 2s residual potential of the sample. The results are expressed as the arithmetic mean and sample standard deviation of 18 samples.
[0193] This test evaluates the ability of the actual system path, consisting of the main electrostatic dissipation area of the packaging material, conductive contact parts, conductive turnover container, grounding connector and 1MΩ safety resistor, to discharge the charge on the charged metal plate. It is not used to characterize the charge decay capability of the packaging material's own surface, nor does it evaluate the discharge shielding performance of the packaging system.
[0194] Preset composite deviation state:
[0195] Each sample was accepted in turn:
[0196] 1. The second main surface is offset laterally by 0.35 mm relative to the first main surface;
[0197] 2. The second main surface is offset by 0.25mm along the machine direction;
[0198] 3. The carbon-containing functional unit is enlarged by 0.30mm in the cutting direction;
[0199] 4. The die-cutting line is offset by 0.25mm towards the main static dissipation area;
[0200] 5. Treat at 40℃ and 90% relative humidity for 168 hours;
[0201] 6. Bend 180° repeatedly 10 times with a radius of 2mm;
[0202] 7.9N load, reciprocating friction 50 times.
[0203] The above positional deviations are the combined deviation conditions preset in this experiment; the positional deviation distribution and its 95th percentile value in the mass production process were not measured in this experiment.
[0204] Functional ink formulation:
[0205] All the following application solutions are calculated based on a production volume of 1000.00g. The measured non-volatile content of the WPU master dispersion is converted to 40.0wt%; in actual preparation, the amounts of WPU master dispersion and deionized water should be adjusted according to the measured non-volatile content of the corresponding batch.
[0206] WPU fiber sealing primer:
[0207] Weigh 750.00g of WPU master dispersion and 250.00g of deionized water. First, add the deionized water to a clean mixing tank and stir at 300rpm. Slowly add the WPU master dispersion over 5 minutes. After the addition is complete, continue stirring for 15 minutes to obtain a WPU fiber sealing primer with a total mass of 1000.00g and a total solid content of 30.0wt%.
[0208] The center contains carbon-containing ink that dissipates:
[0209] Weigh out 682.50 g of WPU master dispersion, 27.00 g of VULCAN XC72R conductive carbon black, and 290.50 g of deionized water, totaling 1000.00 g. The total solid content of the resulting carbon-containing dissipative ink is 30.0 wt%; based on a combined dry mass of conductive carbon black and WPU of 100 wt%, the conductive carbon black content is 9 wt%, and the WPU content is 91 wt%.
[0210] 7wt% conductive carbon black dissipative ink:
[0211] Weigh out 697.50g of WPU master dispersion, 21.00g of VULCAN XC72R conductive carbon black, and 281.50g of deionized water, totaling 1000.00g. The total solid content of the resulting carbon-containing dissipative ink is 30.0wt%; based on a combined dry mass of conductive carbon black and WPU of 100wt%, the conductive carbon black content is 7wt%, with WPU as the balance.
[0212] 11wt% conductive carbon black dissipative ink:
[0213] Weigh out 667.50g of WPU master dispersion, 33.00g of VULCAN XC72R conductive carbon black, and 299.50g of deionized water, totaling 1000.00g. The total solid content of the resulting carbon-containing dissipative ink is 30.0wt%; based on a combined dry mass of conductive carbon black and WPU of 100wt%, the conductive carbon black content is 11wt%, with WPU as the balance.
[0214] 13wt% conductive carbon black dissipative ink:
[0215] Weigh out 652.50g of WPU master dispersion, 39.00g of VULCAN XC72R conductive carbon black, and 308.50g of deionized water, totaling 1000.00g. The total solid content of the resulting carbon-containing dissipative ink is 30.0wt%; based on a combined dry mass of conductive carbon black and WPU of 100wt%, the conductive carbon black content is 13wt% and the WPU content is 87wt%.
[0216] General preparation process for carbon-containing consumable inks:
[0217] Step 1: Add all deionized water and 20% of the total WPU master dispersion to the ink mixing tank, and stir at 500 rpm for 5 min.
[0218] Step 2: Add the conductive carbon black slowly in 5 batches, stirring for 2 minutes after each batch is added. Add the next batch only after the previous batch of carbon black has been completely wetted.
[0219] Step 3: After all the conductive carbon black is added, disperse it for 20 minutes at 8000 rpm using a rotor-stator disperser, and control the temperature of the liquid to be no higher than 35℃.
[0220] Step 4: Add the remaining WPU master dispersion and disperse at 3000 rpm for 10 min.
[0221] Step 5: Filter using a 50μm clean screen and vacuum degas for 10 minutes under an absolute pressure of 20-30kPa to obtain carbon-containing dissipative ink.
[0222] Central PHBV / WPU carbon-free fiber-fixing ink:
[0223] Weigh out 67.20g of PV3000G-M10 micro powder, 432.00g of WPU master dispersion, and 500.80g of deionized water, totaling 1000.00g. The resulting carbon-free solid fiber ink has a polymer solid content of 24.0wt%; based on the total mass of PHBV and WPU polymer solids as 100wt%, the PHBV content is 28wt% and the WPU content is 72wt%.
[0224] PHBV 20wt% Carbon-Free Fiber-Based Ink:
[0225] Weigh out 48.00g of PV3000G-M10 micro powder, 480.00g of WPU master dispersion, and 472.00g of deionized water, totaling 1000.00g. The resulting carbon-free solid fiber ink has a polymer solid content of 24.0wt%; based on a total polymer solid mass of PHBV and WPU of 100wt%, the PHBV content is 20wt%, with WPU as the balance.
[0226] PHBV 35wt% Carbon-Free Fiber-Based Ink:
[0227] Weigh out 84.00g of PV3000G-M10 micro powder, 390.00g of WPU master dispersion, and 526.00g of deionized water, totaling 1000.00g. The resulting carbon-free solid fiber ink has a polymer solid content of 24.0wt%; based on a total polymer solid mass of PHBV and WPU of 100wt%, the PHBV content is 35wt%, with WPU as the balance.
[0228] WPU Carbonless Reference Ink:
[0229] Weigh out 600.00g of WPU master dispersion and 400.00g of deionized water, totaling 1000.00g. The resulting control ink has a polymer solids content of 24.0wt%, and all of its polymer solids are WPU, without PHBV or conductive carbon black.
[0230] PHBV / WPU Carbon-Free Fiber-Based Ink General Formulation Process:
[0231] Step 1: Add all deionized water and WPU master dispersion to a clean ink mixing tank, and stir at 500 rpm for 10 minutes to dilute the WPU evenly.
[0232] Step 2: Add PV3000G-M10 slowly in 10 batches, stirring for 2 minutes after each batch is added; add the next batch only after the surface of the previous batch of micro powder has been completely wetted and no floating dry powder is observed.
[0233] Step 3: After all the PHBV micro powder is added, disperse it for 20 minutes at 5000 rpm using a rotor-stator disperser, and control the temperature of the liquid to be no higher than 35℃.
[0234] Step 4: Continue stirring the dispersion at 300 rpm for 30 min to allow the PHBV micropowder to fully equilibrate in the WPU aqueous phase.
[0235] Step 5: Filter using a 50μm clean screen and vacuum degas for 10 minutes under an absolute pressure of 20-30kPa to obtain PHBV / WPU carbon-free solid fiber ink.
[0236] Step 6: After preparation, and after 4 hours and 8 hours of circulation, the non-volatile matter content, pH, apparent viscosity, and D2 content are measured. 10 D 50 D 90 50μm sieve residue and sedimentation status. The apparent viscosity change rate after 8 hours of circulation is ≤10%, D 90 The batch release conditions for PHBV / WPU carbon-free fiber-fixed ink are: a change rate of ≤20%, no gel or coarse particles on the 50μm screen that affect delivery or printing, and no sedimentation that affects uniform ink supply.
[0237] General preparation process for packaging materials used in the examples:
[0238] Step 1: Condition the paper base in an environment of 23±2℃ and 50%±5% relative humidity for 48 hours, and vacuum dust removal is performed on the two main surfaces respectively; then, WPU solid fiber sealing primer is applied to the full surface of the two main surfaces, and water is removed in the middle under 60℃ hot air conditions to obtain a paper base with a double-sided continuous WPU solid fiber sealing bottom layer.
[0239] Step 2: Prepare carbon-containing dissipative ink and PHBV / WPU carbon-free solid fiber ink respectively according to the general preparation process of carbon-containing dissipative ink and the general preparation process of PHBV / WPU carbon-free solid fiber ink.
[0240] Step 3: Using the paper web edge registration mark as a reference, form the electrostatic dissipation main area, the cross-plane phase-shifting functional mapping transition area, and the PHBV / WPU carbon-free terminal corridor on the first and second main surfaces sequentially or simultaneously, so that the carbon-containing dissipation pattern on each main surface is continuously connected to the electrostatic dissipation main area on the same surface, and a PHBV / WPU carbon-free fiber-fixed pattern is formed on the opposite surface, so that the cross-plane coverage ratio in both directions is not less than 95%; and a continuous WPU flexible carbon-free buffer zone is formed between the cross-plane phase-shifting functional mapping transition area and the terminal corridor.
[0241] When an interdigitated cross-surface reverse registration structure is adopted, phase-staggered carbon dissipation functional units are formed in each pattern cycle, and the PHA / WPU carbon-free fiber-fixing functional units on the two main surfaces are projected to intersect to retain the common carbon-free interval on both sides.
[0242] When a dual-phase non-collinear path structure is adopted, a carbon-containing dissipation path and a PHBV / WPU carbon-free fiber-fixing path are formed on the two main surfaces respectively. The carbon-containing dissipation path on the first main surface and the PHBV / WPU carbon-free fiber-fixing path on the second main surface form a first set of cross-surface corresponding paths, and the carbon-containing dissipation path on the second main surface and the PHBV / WPU carbon-free fiber-fixing path on the first main surface form a second set of cross-surface corresponding paths, and the cross-surface coverage ratio in both directions is not less than 95%.
[0243] Step 4: After printing on each main surface, flash dry at 60℃ for 30 seconds, then enter the common final drying section, controlling the actual maximum temperature of the paper web to be 70-85℃, so that WPU forms a continuous film-forming phase and PHBV forms a dispersed phase or phase separation domain fixed by WPU; then humidify in an environment of 23±2℃ and 50%±5% relative humidity for 24 hours.
[0244] Step 5: Use a dual-sided machine vision system to detect the final dry pattern, and calculate the carbon-containing projection overlap ratio, the cross-surface coverage ratio in two directions, the common projection width of the terminal corridor, and the in-plane net distance from the predetermined tangent to the actual carbon-containing area.
[0245] Step 6: For the paper web that meets the structural requirements, perform die cutting within the common projection range of the PHBV / WPU carbonless terminal corridor on the two main surfaces, and vacuum dust removal on the two main surfaces and the final cut edge of the finished product to obtain the packaging material.
[0246] Example
[0247] Example 1:
[0248] UPM Fine C 90g / m 2 Paper base.
[0249] The WPU base layer uses the aforementioned WPU fiber sealing primer, with a single-sided dry coating amount of 1.2 g / m². 2 The electrostatic dissipation main area uses the aforementioned carbon-containing dissipation ink, with a single-sided dry coating weight of 2.5 g / m². 2 The PHBV / WPU carbonless fiber-fixing functional unit and the PHBV / WPU carbonless terminal corridor use the aforementioned central PHBV / WPU carbonless fiber-fixing ink, with a dry coating weight of 2.2 g / m² in the printed area. 2 .
[0250] The width of the interdigitated cross-face reverse fitting transition zone is 4.0mm, the width of the WPU flexible carbon-free buffer zone is 2.0mm, the width of the PHBV / WPU carbon-free terminal corridor is 4.0mm, and the total width of the decoupling corridor is 10.0mm.
[0251] The pattern period is 6.0 mm. Within each pattern period, the length of the carbon dissipation functional unit on the first and second main surfaces is 2.4 mm, and the two are phase-shifted along a direction parallel to the final cut edge of the finished product; the carbon area coverage of each main surface is 40%, and a carbon-free interval is retained on both sides outside the carbon units on the two main surfaces.
[0252] The carbon-containing dissipation functional unit on the first main surface and the carbon-free fiber-fixing functional unit on the second main surface form a first-direction cross-face corresponding to each other. The carbon-containing dissipation functional unit on the second main surface and the carbon-free fiber-fixing functional unit on the first main surface form a second-direction cross-face corresponding to each other. The cross-face coverage ratio in both directions is not less than 95%.
[0253] The actual highest temperature of the paper web during the final drying stage was 78±3℃.
[0254] The final dry-state bifacial geometric extrema of Example 1 are shown in Table 11.
[0255] Example 2:
[0256] Except for the PHBV / WPU carbon-free solid fiber ink which uses the aforementioned PHBV 20wt% carbon-free solid fiber ink, the other raw materials, structural dimensions, dry coating amount and preparation process are the same as in Example 1.
[0257] Example 3:
[0258] Except for the PHBV / WPU carbon-free solid fiber ink which uses the aforementioned PHBV 35wt% carbon-free solid fiber ink, the other raw materials, structural dimensions, dry coating amount and preparation process are the same as in Example 1.
[0259] Example 4:
[0260] Except for the carbon dissipative ink which uses the aforementioned conductive carbon black 7wt% dissipative ink, the other raw materials, structural dimensions, dry coating amount and preparation process are the same as in Example 1.
[0261] Example 5:
[0262] Except for the carbon dissipative ink which uses the aforementioned 11wt% conductive carbon black dissipative ink, the other raw materials, structural dimensions, dry coating amount and preparation process are the same as in Example 1.
[0263] Example 6:
[0264] The dry coating weight of the WPU base layer on one side is 0.8 g / m². 2 The single-sided dry coating weight of the electrostatic dissipation main area is 2.0 g / m². 2 The dry coating weight of the PHBV / WPU carbon-free fiber-fixing functional unit and the printed area of the PHBV / WPU carbon-free terminal corridor is 1.5 g / m². 2 .
[0265] The remaining raw materials, structural dimensions, and preparation process are the same as in Example 1.
[0266] Example 7:
[0267] The dry coating weight of the WPU base layer on one side is 2.0 g / m². 2 The single-sided dry coating weight of the electrostatic dissipation main area is 3.0 g / m². 2 The dry coating weight of the PHBV / WPU carbon-free fiber-fixing functional unit and the printed area of the PHBV / WPU carbon-free terminal corridor is 3.0 g / m². 2 .
[0268] The remaining raw materials, structural dimensions, and preparation process are the same as in Example 1.
[0269] Example 8:
[0270] UPM Fine C 70g / m 2 Paper base.
[0271] The width of the interdigitated cross-face reverse fitting transition zone is 3.5mm, the width of the WPU flexible carbon-free buffer zone is 1.5mm, the width of the PHBV / WPU carbon-free terminal corridor is 3.0mm, and the total width of the decoupling corridor is 8.0mm.
[0272] The pattern period is 4.0 mm, and the carbon area coverage of each main surface is 20%. The final dry-state bifacial geometric extremes of Example 8 are shown in Table 11.
[0273] The remaining formulation, dry coating amount, and preparation process are the same as in Example 1.
[0274] Example 9:
[0275] UPM Fine C 110g / m 2 Paper base; PUR-MATT 310 is used for the solid fiber sealing underlayer, carbon-containing dissipative ink and the carbon-free solid fiber ink PHBV / WPU.
[0276] The width of the interdigitated cross-face reverse fitting transition zone is 5.0mm, the width of the WPU flexible carbon-free buffer zone is 3.0mm, the width of the PHBV / WPU carbon-free terminal corridor is 5.0mm, and the total width of the decoupling corridor is 13.0mm.
[0277] The final dry-state bifacial geometric extreme values of Example 9 are shown in Table 11, and the bifacial surface resistance results under low and medium humidity conditions are shown in Table 10.
[0278] The remaining formulation, dry coating amount, and preparation process are the same as in Example 1.
[0279] Example 10:
[0280] UPM Fine C 90g / m 2 Paper base.
[0281] The width of the interdigitated cross-face reverse fitting transition zone is 4.0mm, the width of the WPU flexible carbon-free buffer zone is 2.5mm, the width of the PHBV / WPU carbon-free terminal corridor is 4.5mm, and the total width of the decoupling corridor is 11.0mm.
[0282] The final dry-state bifacial geometric extrema of Example 10 are shown in Table 11.
[0283] The remaining formulation, dry coating amount, and preparation process are the same as in Example 1.
[0284] Example 11:
[0285] A dual-phase, non-collinear PHBV / WPU path structure is adopted. A carbon-containing dissipation path is set on the first and second main surfaces, which are continuously connected to the electrostatic dissipation main region on the same plane. The carbon-containing dissipation path on the first main surface and the PHBV / WPU carbon-free fiber-fixing path on the second main surface form the first set of cross-plane corresponding paths, and the carbon-containing dissipation path on the second main surface and the PHBV / WPU carbon-free fiber-fixing path on the first main surface form the second set of cross-plane corresponding paths. The cross-plane coverage ratio in both directions is not less than 95%.
[0286] The width of the transition zone of the two phase-shifted non-collinear paths is 6.0 mm. The solid width of the two PHBV / WPU carbon-free fiber-fixing paths is 1.0 mm. The amplitude of the centerline on one side is 0.45 mm and the period is 6.0 mm. The period starting point of the carbon-containing dissipation path in each group is used as the phase reference of the group. The phase difference between the corresponding path of the first cross-face and the corresponding path of the second cross-face is 50% of the period. The shortest net distance between the actual boundaries of the two PHBV / WPU carbon-free fiber-fixing paths after projection is 1.2 mm.
[0287] The two sets of cross-face corresponding paths and the side near the final cut edge of the finished product are covered by a continuous carbon-free area; a 2.0 mm wide WPU flexible carbon-free buffer zone and a 4.0 mm wide PHBV / WPU carbon-free terminal corridor are set on the outside. The total amount of PHBV, WPU and conductive carbon black and the common final drying conditions are the same as in Example 1.
[0288] The final dry-state bifacial geometric extrema of Example 11 are shown in Table 11.
[0289] Comparative example.
[0290] Comparative Example 1:
[0291] No interdigitated cross-face anti-overlapping structure is set, no independent WPU flexible carbon-free buffer zone is set, and only a WPU carbon-free solid fiber layer is set in the terminal area.
[0292] The transition zone is 4.0 mm wide, the WPU carbon-free terminal area is 6.0 mm wide, and the total width of the decoupling corridor is 10.0 mm.
[0293] The terminal area used the aforementioned WPU carbonless control ink, with the dry coating weight adjusted to 1.47 g / m². 2 This makes the total amount of terminal polymer per unit cutting edge length similar to that in Example 1.
[0294] The remaining paper base, WPU underlayer, carbon ink, dry coating amount of electrostatic dissipation main area, drying and die-cutting conditions are the same as in Example 1.
[0295] Comparative Example 2:
[0296] The interdigitated cross-plane anti-overlapping structure of Example 1 is adopted, without setting an independent WPU flexible carbon-free buffer zone, and the terminal area uses a WPU carbon-free layer.
[0297] The transition zone is 4.0 mm wide, the WPU carbon-free terminal area is 6.0 mm wide, and the total width of the decoupling corridor is 10.0 mm.
[0298] The remaining conditions are the same as in Example 1.
[0299] Comparative Example 3:
[0300] Instead of using an interdigitated cross-surface reverse registration structure, the carbon-containing functional units on the two main surfaces are set with the same nominal pattern coordinates, and no phase offset is applied along the direction parallel to the final cut edge of the finished product; a WPU flexible carbon-free buffer zone with a width of 2.0mm is set, and the terminal corridor uses a WPU carbon-free layer.
[0301] The remaining structural dimensions and preparation conditions are the same as in Example 1.
[0302] Comparative Example 4:
[0303] It does not adopt an interdigitated cross-plane anti-overlapping structure and does not set an independent WPU flexible carbon-free buffer zone; it sets a 6.0mm continuous PHBV / WPU terminal area.
[0304] The dry coating weight of the continuous PHBV / WPU terminal region is 1.47 g / m². 2 This makes the total amount of PHBV and WPU per unit cutting edge length similar to that in Example 1.
[0305] The remaining conditions are the same as in Example 1.
[0306] Comparative Example 5:
[0307] The interdigitated cross-plane reverse registration structure of Example 1 and the WPU flexible carbonless buffer with a width of 2.0 mm are used, and the aforementioned WPU carbonless reference ink is used in the terminal corridor.
[0308] The width of the terminal corridor and the amount of dry coating on the printed area are the same as in Example 1.
[0309] The remaining conditions are the same as in Example 1.
[0310] Comparative Example 6:
[0311] The interdigitated cross-plane anti-overlapping structure of Example 1 is adopted, without setting an independent WPU flexible carbon-free buffer zone.
[0312] The width of the carbonless terminal corridor for PHBV / WPU was increased from 4.0mm to 6.0mm, while maintaining the total width of the decoupling corridor at 10.0mm; the dry coating amount in the terminal area was adjusted to 1.47g / m². 2 This makes the total amount of PHBV and WPU per unit cutting edge length similar to that in Example 1.
[0313] The remaining conditions are the same as in Example 1.
[0314] Comparative Example 7:
[0315] Instead of using an interdigitated cross-surface anti-overlapping structure, the carbon-containing functional units on the two main surfaces are set with the same nominal pattern coordinates, and no phase offset is applied along the direction parallel to the final cut edge of the finished product.
[0316] The 2.0 mm wide WPU flexible carbon-free buffer zone and the 4.0 mm wide PHBV / WPU carbon-free terminal corridor were retained, and the remaining formulations, dry coating amounts, and preparation conditions were the same as in Example 1.
[0317] Comparative Example 8:
[0318] The 2.0 mm wide WPU flexible carbonless buffer zone and the 4.0 mm wide PHBV / WPU carbonless terminal corridor in Example 1 are combined into a continuous 6.0 mm wide PHBV / WPU broadband.
[0319] The continuous PHBV / WPU broadband uses the aforementioned central PHBV / WPU carbon-free fiber-fixing ink, with a dry coating weight of 1.47 g / m. 2 This makes the total amount of PHBV and WPU per unit cutting edge length similar to that in Example 1.
[0320] The remaining conditions are the same as in Example 1.
[0321] Comparative Example 9:
[0322] It adopts a common double-sided staggered coating structure.
[0323] The carbon-containing functional area termination boundary of the first main surface and the carbon-containing functional area termination boundary of the second main surface are offset by 2.0 mm along the direction from the electrostatic dissipation main area to the final cut edge of the finished product, but do not form carbon-containing-PHBV cross-face corresponding units that are alternately arranged along the direction parallel to the final cut edge.
[0324] The projection overlap ratio of the two carbon-containing areas is controlled at 20% to 30%, and the WPU flexible carbon-free buffer zone and PHBV / WPU carbon-free terminal corridor are retained on both sides respectively.
[0325] The remaining material usage, total width of the decoupling corridor, and preparation conditions are the same as in Example 1.
[0326] Comparative Example 10:
[0327] Two straight PHBV / WPU strips are set in the transition zone of each main surface, extending continuously parallel to the final cut edge direction.
[0328] Each straight strip is 1.0 mm wide, and the net distance between two straight strips is 1.2 mm; the total amount of PHBV, WPU and carbon black is the same as in Example 1.
[0329] The 2.0mm wide WPU flexible carbon-free buffer zone and the 4.0mm wide PHBV / WPU carbon-free terminal corridor are retained, and the cross-finger cross-face carbon-containing-PHBV function is not set.
[0330] Comparative Example 11:
[0331] The same total amounts of PHBV, WPU, and carbon black as in Example 1 were used.
[0332] The terminal corridor uses WPU carbonless reference ink, and the PHBV / WPU layer originally located in the terminal corridor is moved to the non-cut edge area inside the electrostatic dissipation main area, more than 30mm away from the final cut edge of the finished product.
[0333] The inner PHBV / WPU layer does not participate in the final edge cutting and fiber fixation.
[0334] The remaining interdigitated structure, WPU flexible carbon-free buffer, dry coating amount, drying and die-cutting conditions are the same as in Example 1.
[0335] Comparative Example 12:
[0336] Comparative Example 12 was identical to Example 1 except that the conductive carbon black content in the carbon dissipative ink was 13 wt% of the total mass of functional solids. Other components included the paper base, WPU solid fiber sealing underlayer, PHBV / WPU carbon-free solid fiber ink, pattern cycle, carbon area coverage, interdigitated cross-surface anti-overlapping structure, WPU flexible carbon-free buffer zone, PHBV / WPU carbon-free terminal corridor, dry coating amount, drying conditions, die-cutting conditions, and dust removal conditions.
[0337] Comparative Example 12 has the same spatial structure as Example 1, and its conductive carbon black content is 13 wt%, which is higher than the comparison range of 7-11 wt%, and is used to evaluate the changes in clean performance and mechanical stability after further increasing the content.
[0338] Application examples
[0339] Application Example 1: Simulated turnover test of conductive turnover box lining.
[0340] Experimental Description: This experiment was used to evaluate the particle release, black transfer, cracking, and electrostatic dissipation stability of Examples 1-11 and Comparative Examples 1-12 as reusable conductive turnover box liners after loading, vibration, handling, and repeated loading and unloading. Each sample was cut into 300mm × 300mm liner sheets, with the main electrostatic dissipation area being 250mm × 250mm. The final cut edges of the finished product were fitted with the structures specified for the corresponding sample. After cutting, a vacuum dust removal device was used to remove dust from both main surfaces for 30 seconds at a negative pressure of 20kPa. The liner sheets were laid flat at the bottom of the turnover box, with the main electrostatic dissipation area facing the inside of the box. The liner sheets had internal dimensions of 400mm × 320mm × 250mm and a surface resistivity of 10 Ω·cm. 3 ~10 6 The conductive polypropylene turnover box of Ω contains four conductive trays, each tray holding 50 packaged simulants without exposed chips, exposed gold fingers, or sensitive optical surfaces. The total mass of the simulants is 6.0 ± 0.2 kg. Each cycle involves the following steps: laying the inner liner, loading the tray, closing the box lid, vibrating for 5 minutes at 1 Hz on an SM 30 B control horizontal reciprocating oscillator with a 50 mm stroke component, manually transporting for 30 m along a flat path, opening the lid and removing the tray, inspecting the surface, bends, and final cut edges of the inner liner, and reloading. Each liner undergoes 20 consecutive cycles. Before turnover and after 20 cycles, the particle release per unit cut edge length with a particle size not less than 1 μm and the black transfer ΔL of the white clean PET acceptor membrane are measured using the aforementioned method. * The surface resistance of the decoupled corridor with total crack length per unit length and electrostatic dissipation main area under relative humidity of 12%±3% was calculated, and the order of magnitude of the change in surface resistance before and after turnover was calculated.
[0341] Table 4. Results of simulated turnover test of conductive turnover box lining (mean ± sample standard deviation, n = 18).
[0342]
[0343] Note: The surface resistivity of Comparative Example 12 is on the order of less than 1×10⁻⁶. 6The resistance drift of Ω was not included in the horizontal comparison in this table; the results of particle, black transfer and cracking were still used to evaluate the cleanliness and mechanical stability after the conductive carbon black content was increased to 13wt%.
[0344] Analysis: The particle size after 20 cycles of Examples 1 to 11 was 640±41 to 1099±79 particles / m³. -1 Black transfer ΔL * The crack strength ranged from 0.97±0.06 to 2.07±0.16 mm, and the total crack length ranged from 5.3±0.6 to 12.1±0.9 mm·m. -1 Comparative Examples 1-4, without simultaneously setting the cross-plane phase-shifting functional mapping structure, the independent WPU flexible carbon-free buffer zone, and the PHBV / WPU carbon-free terminal corridor, showed higher particle size, black transfer, and cracking after 20 cycles compared to Example 1. Comparative Examples 5, 7, and 10 had some indicators close to the range of the Examples under the same cycle conditions, but their particle size, black transfer, or cracking was still higher than that of Example 1. Comparative Example 12 had a conductive carbon black content of 13 wt%, and its black transfer ΔL... * The value was 2.74 ± 0.17, which is higher than that of Example 5, where the conductive carbon black content was 11 wt%, indicating that further increasing the conductive carbon black content did not simultaneously improve the cleanliness after turnover.
[0345] Application Example 2: Reciprocating insertion and removal test of electronic component isolation plates.
[0346] Experimental Description: This experiment was used to evaluate the friction particles, black transfer, warpage, delamination, and electrical stability of Examples 1-11 and Comparative Examples 1-12 as electronic component trays or cassette separators after repeated insertion, extraction, and humid heat storage. Each sample was cut into 250mm × 180mm separator sheets, with the specified final cut edge structure around the perimeter. Before testing, the separator sheets were placed on a precision level platform, and the heights at the four corners and center were measured. The difference between the highest and lowest points was taken as the initial warpage height.
[0347] An IAI RCP6-SA7C electric linear reciprocating platform is used, with an effective stroke of 250 mm and a ball screw lead of 8 mm, controlled by a PCON-CB controller. One end of the isolation plate along its 250 mm length is fixed to a low-particle traction fixture, causing the isolation plate to reciprocate along its length.
[0348] Two clean polypropylene pallet simulants are used to clamp the isolation plate. The opposing surfaces of the two pallet simulants each have a flat contact strip extending along the width of the isolation plate. Each contact strip is 20.0 mm long in the reciprocating direction and 180.0 mm wide laterally. Areas outside the contact strips are recessed by at least 0.5 mm relative to the contact surface to avoid non-designated areas sharing the normal load. The lower pallet simulant is fixed to the test bench, and the upper pallet simulant is connected to the self-aligning pressure plate of the ZwickRoell zwickiLineZ0.5 TH.
[0349] The specified contact area A is 20.0 mm × 180.0 mm, which is 0.00360 m². 2 The average normal pressure of the pallet is calculated according to p = F / A, where F is the normal force measured by the Xforce HP 500N load sensor. When the target pressure value is 2.0 kPa, the corresponding normal force is 7.20 N; the allowable normal force range corresponding to 2.0 ± 0.2 kPa is 6.48 to 7.92 N.
[0350] The load cell was calibrated according to ISO 7500-1:2018. Before testing each sample, the load cell was zeroed, and the self-aligning pressure plate was lowered at a speed of 10 mm / min until the normal force reached 7.20 N. After holding this position for 10 seconds, the system switched to force closed-loop control mode, maintaining the normal force between 6.48 and 7.92 N throughout the insertion and extraction test. The normal force was continuously recorded at a sampling frequency of 100 Hz, and the average normal pressure on the tray was calculated based on the measured force value and the specified contact area.
[0351] The electric linear reciprocating platform has an insertion and withdrawal stroke of 220 mm, an insertion speed of 100 mm / s, and an acceleration of 0.2G. One complete 220 mm insertion and withdrawal is counted as one reciprocating cycle, and each specimen undergoes 50 reciprocating cycles. A 1-minute pause is taken after every 10 reciprocating cycles, during which the normal load is maintained. If the average normal force of any reciprocating cycle exceeds 6.48–7.92 N, the insertion and withdrawal test for that specimen is restarted.
[0352] After insertion and removal, the isolation sheet was treated at 40±2℃ and 90%±5% relative humidity for 168 hours, and then restored at 23±2℃ and 50%±5% relative humidity for 24 hours. Subsequently, the particle release per unit cut length and the black transfer ΔL of the white PET receptor membrane were measured according to the aforementioned method. * The maximum warpage height of the isolation sheet, the proportion of delamination area after humid heat, and the resistance drift before and after the treatment of the main area for electrostatic dissipation.
[0353] Table 5 Results of repeated insertion and removal tests of electronic component isolation plates (mean ± sample standard deviation, n = 18).
[0354]
[0355] Note: The surface resistivity of Comparative Example 12 is on the order of less than 1×10⁻⁶. 6 The resistance drift of Ω is not included in the horizontal comparison in this table.
[0356] Analysis: The particle size after 50 cycles of insertion and extraction and damp heat treatment in Examples 1 to 11 was 562±36 to 965±47 particles / m³. -1 Black transfer ΔL * The values ranged from 0.90±0.06 to 1.93±0.12 mm, with a maximum warpage height of 1.31±0.11 to 2.33±0.08 mm and a delamination area of 0.45±0.06% to 1.35±0.19%. Comparative Examples 1 to 4 showed higher particle size distribution, black transfer, warpage, and delamination than Example 1, indicating that the lack of a cross-plane phase-shifting functional mapping structure, an independent WPU flexible carbon-free buffer zone, or a PHBV / WPU carbon-free terminal corridor led to decreased structural stability after repeated insertion / removal and damp heat treatment. Some indicators of Comparative Examples 5 to 7 and Comparative Example 10 were between those of the Example and the other comparative examples. The black transfer ΔL of Comparative Example 12... * The value was 2.56 ± 0.16, higher than 1.76 ± 0.11 in Example 5, indicating that increasing the conductive carbon black content to 13 wt% did not improve the triboelectric cleanliness of the separator.
[0357] Application Example 3: Bending and loading / unloading test of electronic component turnover sleeve.
[0358] Experimental Description: This experiment was used to evaluate the crack propagation, edge particle size, black transfer, and dimensional stability of electronic component turnover sleeves manufactured in Examples 1-11 and Comparative Examples 1-12 after bending in different directions, repeated fitting, and damp heat treatment. Each sample was cut into 300mm × 160mm sheets. Indentation lines parallel and perpendicular to the final cut edge of the finished product were made on the sheets, with an indentation depth of 25% ± 5% of the paper base thickness, without cutting the paper base. The sheets were then folded into rectangular sleeves with an inner circumference of 250mm and an overlap width of 15mm, secured with removable mechanical clips without adhesive. A tube assembly with external dimensions matching the sleeve's internal dimensions was used as a simulation. Each fitting cycle consisted of fully fitting the sleeve into the tube assembly, holding for 10 seconds, withdrawing at a speed of 100mm / s, checking the bending area and final cut edge, and refitting. Each piece was repeated 30 times. After the assembly was completed, the samples were treated at 40±2℃ and 90%±5% relative humidity for 168 hours, and then recovered at 23±2℃ and 50%±5% relative humidity for 24 hours. Next, the samples were bent 180° repeatedly along the two indentation lines with a bending radius of 2 mm each, 10 times in total. Subsequently, the total crack length parallel and perpendicular to the final cut edge direction, the number of particles per unit cut edge length, and the black transfer ΔL of the white PET acceptor membrane were measured using the aforementioned method. * And the maximum rate of change of the sleeve length and width before and after humid heat.
[0359] Table 6 Results of bending and loading / unloading tests on electronic component turnover sleeves (mean ± sample standard deviation, n = 18).
[0360]
[0361] Analysis: In Examples 1 to 11, the cracks formed during bending perpendicular to the final cut edge of the finished product were all higher than those in the parallel direction, indicating that the bending direction affects crack propagation. The parallel bending crack lengths in the examples ranged from 5.5 ± 0.4 to 12.6 ± 1.3 mm·m. -1 The vertical bending crack length was 7.3±0.5~16.6±1.4 mm·m. -1 The number of shredded particles is 608±33~1045±50 per m. -1 Black transfer ΔL * The values ranged from 0.99±0.09 to 2.12±0.20. The bidirectional cracking, graining, and black transfer in Comparative Examples 1 to 4 were significantly higher than in Example 1. Some indicators of Comparative Examples 5 and 10 were between those of the Example and the other Comparative Examples, but their cracking and black transfer were still higher than those of the corresponding intact structures. The black transfer ΔL in Comparative Example 12... * The value was 2.83 ± 0.18, which was higher than 1.94 ± 0.18 in Example 5, indicating that increasing the conductive carbon black content from 11 wt% to 13 wt% did not improve the cleanliness after sleeve loading and unloading.
[0362] Application Example 4: Verification of Preset Composite Deviation State.
[0363] Experimental Description: This experiment was used to evaluate the comprehensive failure control capabilities of Examples 1-11 and Comparative Examples 1-11 under conditions of double-sided registration misalignment, carbon-containing boundary expansion, die-cutting misalignment, damp heat, bending, and friction occurring simultaneously. Comparative Example 12 was not included in the composite evaluation in Table 7 because it was not included in the lateral comparison of surface resistance in this application example. For each sample, during the pattern design, plate-making, or die-cutting stages, the second main surface was offset laterally by 0.35 mm relative to the first main surface, offset along the machine direction by 0.25 mm, the carbon-containing dissipation pattern was expanded by 0.30 mm towards the final cut edge of the finished product, and the die-cutting line was offset by 0.25 mm towards the main electrostatic dissipation area. A 0.10 mm image edge recognition error was also included in the design evaluation. After obtaining the final product according to the above deviations, it was first treated at 40±2℃ and 90%±5% relative humidity for 168 hours, and then recovered at 23±2℃ and 50%±5% relative humidity for 24 hours. Subsequently, it was bent 180° back and forth 10 times along a circular shaft with a radius of 2 mm, and then rubbed back and forth 50 times under a 9N load using a Sutherland friction tester. After the treatment, the particle release amount per unit tangential length with a particle size of not less than 1 μm and the black transfer ΔL were measured in the aforementioned particle release closed test space according to the aforementioned method. * The total crack length, delamination area, and surface resistance of the main electrostatic dissipation region were evaluated using the aforementioned preset composite evaluation conditions.
[0364] Table 7. Verification results of the preset composite deviation state (number of samples n=18; except for surface resistance, the values are arithmetic mean ± sample standard deviation, and surface resistance is the geometric mean and geometric standard deviation).
[0365]
[0366] Note: The “composite evaluation” in the table is based on the composite evaluation conditions preset in this instruction manual and is only used for cross-sectional comparison of different samples under the same test conditions.
[0367] Examples 1-7, Examples 9-11, Comparative Examples 5 and 10 all reached the preset evaluation value; the particle index of Example 8 did not reach the preset evaluation value; Comparative Examples 1-4, Comparative Examples 6, Comparative Examples 8-9, and Comparative Examples 11 did not reach the preset evaluation value; the black transfer index of Comparative Example 7 did not reach the preset evaluation value.
[0368] Analysis: Under the preset composite deviation conditions, Examples 1-7 and Examples 9-11 achieved the five preset evaluation values. The particle release amount of Example 8 was 1340±88 particles / m³. -1 Slightly higher than 1300 m -1The preset evaluation values were met, and the other four indicators reached their corresponding evaluation values, indicating that the particle control margin of the lower end combination of this size is relatively small. Although Comparative Examples 5 and 10 reached all five preset evaluation values, their particle size, black transfer, crack, and delamination continuity test results were higher than those of Examples 1 and 11, respectively, indicating that the composite evaluation results cannot replace the comparison of continuous data.
[0369] Application Example 5: Test on the linkage trend between the final cut edge of the finished product and the net distance to the actual carbon-containing area and the corridor width.
[0370] Experimental Description: This experiment quantitatively evaluates the impact of the net distance from the final cut edge of the finished product to the nearest actual carbon-containing area, and the corridor structure formed by the combined changes in the width of the WPU flexible carbon-free buffer zone and the PHBV / WPU carbon-free terminal corridor, on particle size, black transfer, carbon black hot spots on the cut surface, and cracks. Performance changes were observed around 4.5 mm and in the range of 5.5–8.0 mm. Net distance groups 1–5 all used UPM Fine C 90g / m² from Example 1. 2 The paper base, carbon-containing dissipative ink in the center, carbon-free fiber-fixed ink in the center (PHBV / WPU), 6.0mm pattern cycle, 40% single-sided carbon coverage, and a phase-staggered interdigitated cross-plane reverse registration structure; the width of the interdigitated cross-plane reverse registration transition zone is fixed at 4.0mm. Different net distances are obtained by changing the width of the WPU flexible carbon-free buffer zone and the PHBV / WPU carbon-free terminal corridor, and the coating area in the non-test area is adjusted so that the total amount of PHBV, WPU, and conductive carbon black used in each group does not exceed ±2%. In groups 1 through 5, the average values of the smaller net distances on both sides of each finished product were 3.00±0.05mm, 4.56±0.03mm, 5.57±0.04mm, 6.58±0.04mm, and 8.08±0.04mm, respectively. The measured minimum net distances for the 18 pieces in groups 2, 3, 4, and 5 were 4.50mm, 5.50mm, 6.50mm, and 8.00mm, respectively. Each group underwent deviation setting, damp heat treatment, recovery, bending, and friction sequentially according to the preset composite deviation state described in Application Example 4. Subsequently, the particle size per unit cut edge length and the black transfer ΔL of the white PET receptor film were measured using the aforementioned method. * The number of carbon black hot spots and the total length of decoupling corridor cracks within the final 100mm cutting edge range confirmed by micro Raman spectroscopy; the net distance is calculated based on the smaller of the measured values of the two main surfaces of each finished product.
[0371] Table 8 Results of the test on the linkage between the final cut edge of the finished product and the net distance to the actual carbon-containing area and the corridor width (mean ± sample standard deviation, n = 18).
[0372]
[0373] Note: For each clearance group, the smaller of the measured clearances between the two main surfaces of each finished product was used for statistical analysis. The minimum measured clearances for the 18 pieces in clearance groups 2, 3, 4, and 5 were 4.50 mm, 5.50 mm, 6.50 mm, and 8.00 mm, respectively. The conductive carbon black content of Comparative Example 12 was 13 wt%, which differed from the 9 wt% used in clearance groups 1 through 5. Therefore, it was not included in the analysis of the correlation between clearance and corridor width.
[0374] Analysis: As the actual carbon-containing clearance and corresponding corridor width increase, the overall levels of particles, black transfer, carbon black hot spots on the cut surface, and cracks decrease. Group 1 showed the highest values for particles, black transfer, carbon black hot spots, and cracks among the five groups. Group 2 had an average clearance of 4.56±0.03 mm on both sides, and the smallest measured clearance of 18 pieces was 4.50 mm, showing a significant decrease in all indicators compared to Group 1. When the average clearance increased from 6.58±0.04 mm to 8.08±0.04 mm, all indicators still improved, but the improvement rate decreased. Group 5 had an average clearance of 8.08 mm, slightly higher than the upper end of the 5.5–8.0 mm range; its results are only used to observe the changing trends after further increases in clearance and corridor width.
[0375] Application Example 6: System grounding, dual humidity surface resistance and dual-sided geometry verification test.
[0376] System grounding and charge decay test:
[0377] This test was used to evaluate the continuous grounding path of a representative packaging system and its ability to discharge the charge carried by a charged metal plate. A conductive polypropylene turnover box with internal dimensions of 400mm×320mm×250mm was used. The packaging material was equipped with four 20mm×30mm conductive contact parts, which were in contact with the inner bottom surface of the turnover box through stainless steel clamps. The stainless steel grounding terminal on the outside of the turnover box was connected to a common grounding point through a grounding wire with a 1MΩ safety resistor in series.
[0378] Examples 1 and 10 constitute System A and System B, respectively, both using the same conductive turnover box, grounding connector, and conductive clamping method. The grounding wire disconnection control is based on System A, except that the grounding wire between the outer grounding terminal of the turnover box and the common grounding point is disconnected. The no-local-dissipation-path control keeps the grounding wire connected, and sets the area where the packaging material contacts the charged metal plate as an area with only a WPU carbon-free surface and no conductive carbon black electrostatic dissipation path.
[0379] The point-to-point resistance of the container's inner surface, the container's point-to-ground resistance, the point-to-ground resistance of the main area of electrostatic dissipation of the packaging material, the continuity of the grounding connection, and charge decay were measured using the methods described above. The container's point-to-ground resistance and the main area of electrostatic dissipation of the packaging material's point-to-ground resistance were measured under actual grounding conditions with a 1MΩ safety resistor in series retained; the measurement results did not deduct the 1MΩ safety resistor. The measurement of the grounding connection continuity did not include the 1MΩ safety resistor.
[0380] A charged metal plate is electrically connected to the testing area of the packaging material via the same conductive clamp. The main electrostatic dissipation area of the packaging material is connected to a common grounding point sequentially through a conductive contact, a conductive turnover box, a grounding connector, and a 1MΩ safety resistor. Starting from +1000V and −1000V respectively, the time required to decay to 100V of the same polarity is recorded; the 2s residual potential of each sample is taken as the larger of the absolute values of the positive and negative polarity test results.
[0381] Table 9 Results of system grounding and charged metal plate charge decay tests [resistance is expressed as geometric mean (GSD), and other continuous results are mean ± sample standard deviation, n = 18].
[0382]
[0383] Note: The point-to-point resistance of the container's inner surface, the container's point-to-ground resistance, and the point-to-ground resistance of the main area of electrostatic dissipation of the packaging material are all expressed as geometric mean, with the geometric standard deviation in parentheses. Grounding connection continuity, decay time, and 2s residual potential are expressed as arithmetic mean ± sample standard deviation. The container's point-to-ground resistance and the main area of electrostatic dissipation of the packaging material's point-to-ground resistance both include the 1MΩ safety resistor connected in series in the grounding connector; the measurement results do not deduct this 1MΩ safety resistor. Grounding connection continuity refers to the metal connection resistance of the conductive clamp, the conductive turnover container's metal grounding terminal, and the grounding connector located on the 1MΩ safety resistor container side, excluding the 1MΩ safety resistor. "—" indicates that there is no continuous metal grounding connection after the grounding wire is disconnected; when the point-to-ground resistance exceeds the test upper limit, it is reported as >1×10. 12 Ω. The 2s residual potential is the larger of the absolute values of the positive and negative polarity test results for each sample.
[0384] Analysis: In systems A and B, the main electrostatic dissipation area of the packaging material forms a continuous grounding path through conductive contacts, a conductive turnover box, and a grounding connector. The average decay time for both positive and negative polarities does not exceed 0.50 s, and the 2-s residual potentials are 18 ± 6 V and 12 ± 4 V, respectively. When the grounding wire is disconnected or the packaging material lacks a local electrostatic dissipation path, the decay time for both positive and negative polarities exceeds 30 s, and the 2-s residual potential increases significantly. This result indicates that a continuous grounding path can accelerate the discharge of charge from charged metal plates electrically connected to this path; the results of this experiment do not represent the decay time of free charges on the surface of the packaging material itself.
[0385] Dual humidity surface resistance test.
[0386] This experiment was used to evaluate the electrostatic dissipation performance of two main surfaces of packaging materials under low and medium humidity conditions. Examples 1, 4, 5, 8, 9, 10, and Comparative Example 1 were selected, with different finished samples used for low and medium humidity conditions. Following the aforementioned surface resistance method, the samples were conditioned for at least 48 hours at 23±2℃ and 12%±3% relative humidity, and at 23±2℃ and 50%±5% relative humidity, respectively. Five non-overlapping locations were measured at the main electrostatic dissipation regions of each of the two main surfaces. The results are expressed as the geometric mean and geometric standard deviation.
[0387] Table 10 shows the surface resistance results of representative samples under dual humidity conditions.
[0388]
[0389] Note: In Example 9, the fiber-bonded sealing substrate, carbon-containing dissipative ink, and PHBV / WPU carbon-free fiber-bonded ink all used PUR-MATT310 as the WPU; the other listed samples used Bayhydrol UH 2889. The surface resistivity results are geometric mean values, and the geometric standard deviation is calculated based on the base-10 logarithm of a single measurement.
[0390] Analysis: The geometric mean of the two principal surface resistivities in Examples 1, 4, 5, 8, 9, and 10 under low and medium humidity conditions is all within 10. 5 ~10 9 The surface resistivity is within the above range. Example 9, using PUR-MATT 310, and Example 1, using Bayhydrol UH 2889, both formed electrostatic dissipation master regions. Comparative Example 1 also had a surface resistivity within the above range, but its particle, black transfer, crack, and delamination results were higher than those of Example 1, indicating that the surface resistivity of the electrostatic dissipation master region cannot independently characterize the cleanliness and mechanical stability of the final cut edge.
[0391] Two-sided geometric extreme value test.
[0392] This experiment was used to determine the final dry-state actual geometric boundary of the cross-surface pattern. Example 1, representing the central structure; Example 8, representing the lower dimension combination; Example 9, representing the upper dimension combination; Example 10, representing a further tightened cross-surface geometric relationship; and Example 11, employing a double-phase non-collinear path structure, were selected. The final dry-state patterns of the two main surfaces were acquired and corrected using the aforementioned double-sided cross-surface projection relationship method. The carbon-containing projection overlap ratio, the cross-surface coverage ratio in both directions, the common projection width of the terminal corridor, and the actual carbon-containing net distance between the two surfaces were calculated.
[0393] Examples 2 to 7 use the same pattern structure, structural dimensions, registration method, and preparation process as Example 1, only changing the PHBV content, conductive carbon black content, or functional layer dry coating amount. Therefore, the same nominal geometry is not repeated in Table 11. Each example listed in Table 11 uses 3 independent preparation batches, with 6 finished products in each batch, for a total of 18 products, and reports the maximum or minimum value among the 18 finished products.
[0394] Table 11. Final dry-state bifacial geometric extrema of representative embodiments.
[0395]
[0396] Note: The first direction coverage ratio is the cross-surface coverage ratio of the carbon-containing dissipation pattern on the first main surface relative to the carbon-free PHA / WPU solid fiber pattern on the second main surface; the second direction coverage ratio is the cross-surface coverage ratio of the carbon-containing dissipation pattern on the second main surface relative to the carbon-free PHA / WPU solid fiber pattern on the first main surface. In Example 11, the minimum actual carbon-containing net distance between the first and second main surfaces is 5.89 mm and 5.84 mm, respectively. The table lists the minimum values after merging the two surfaces.
[0397] Analysis: All embodiments listed in Table 11 meet the requirements of carbon-containing projection overlap ratio ≤ 5%, cross-plane coverage ratio in both directions ≥ 95%, common projection width ≥ 1.0 mm, and actual carbon-containing net distance between the two sides ≥ 4.5 mm. The maximum carbon-containing projection overlap ratio and minimum carbon-containing net distance in Embodiment 8 are closest to the corresponding boundaries; Embodiment 11 shows that the double-phase non-collinear path structure can be controlled using the same final dry-state geometric parameters as the interdigitated cross-plane anti-aperture structure.
[0398] Experimental results and analysis.
[0399] The impact of the combination of the complete structure and the core area:
[0400] Under the preset composite deviation state, the particle release amount and black transfer ΔL of Example 1 * The total crack length and delamination area were 920 m². -1 1.45, 8.0 mm·m -1And 0.8%, compared to 2460 m in Comparative Example 1. -1 5.80, 32.0 mm·m -1 The particle release in Example 1 was reduced by 62.6%, compared to 4.8%. The surface resistance of the main electrostatic dissipation region in both examples was similar, indicating that surface resistance alone cannot reflect the cleanliness and mechanical stability of the final cut edge.
[0401] Comparative Examples 5, 6, and 7 lacked a PHBV / WPU carbon-free terminal corridor, an independent WPU flexible carbon-free buffer zone, or an interdigitated cross-face anti-overlay structure, respectively, and their particle release rates were 1260 particles per m³. -1 1320 units / m -1 and 1190 m -1 Example 1 showed reductions of 27.0%, 30.3%, and 22.7% compared to the three comparative examples, with corresponding reductions in black transfer, cracking, and delamination. These results indicate that the combination of the interdigitated cross-face anti-overlapping structure, the WPU flexible carbon-free buffer zone, and the PHBV / WPU carbon-free terminal corridor corresponds to lower particle release, black transfer, cracking, and delamination.
[0402] The impact of PHBV / WPU carbonless terminal corridor and independent WPU flexible carbonless buffer zone:
[0403] Example 1 and Comparative Example 5 share the same interdigitated cross-face reverse-aperture structure, WPU flexible carbon-free buffer zone, terminal corridor width, and total dry polymer coating weight. The difference lies in that the terminal corridor in Example 1 contains 28 wt% PHBV, while Comparative Example 5 uses WPU of equal dry mass instead of PHBV. Under the preset composite deviation condition, the particle release rates of both are 920 particles per m³. -1 And 1260 m -1 The cracks are 8.0 mm·m. -1 and 14.0 mm·m -1 The layered areas were 0.8% and 1.7%, respectively. In Comparative Example 11, an equal amount of PHBV / WPU layer was moved to a non-cutting edge area more than 30mm from the final cut edge of the finished product; its particle size was 1680 particles per cubic meter. -1 Black transfer ΔL * The value of 3.20 indicates that when the PHBV / WPU layer is placed in the terminal corridor, it can act more directly on the area near the final cut edge.
[0404] Comparative Example 6, with the independent WPU flexible carbon-free buffer zone removed and the PHBV / WPU terminal region continuously expanded, showed 1320 particles, cracks, and delamination per cubic meter. -1 21.0 mm·m -1And 2.2%; Comparative Example 8 combined the WPU flexible carbon-free buffer zone with the PHBV / WPU carbon-free terminal corridor into a continuous PHBV / WPU broadband, with a crack size of 23.5 mm·m. -1 The layered area is 2.5%. The results show that, with similar total carbon-free width and material usage, the partitioning of the independent WPU flexible carbon-free buffer zone and the PHBV / WPU carbon-free terminal corridor can balance flexible buffering and final edge cutting and fiber fixing.
[0405] The impact of cross-plane phase-shifting functional mapping structures:
[0406] Example 1 employs an interdigitated cross-surface reverse registration structure; Comparative Example 7 uses a structure where carbon-containing functional units on two main surfaces are set according to the same nominal pattern coordinates without phase misalignment; and Comparative Example 9 uses a common double-sided boundary misalignment structure. The particle counts of the three examples under a preset composite deviation state are 920 particles per cubic meter. -1 1190 units / m -1 And 1510 m -1 Black transfer ΔL * The values are 1.45, 2.80, and 3.10, respectively. Ordinary double-sided misalignment only changes the boundary position of the two surfaces and does not form a cross-surface functional correspondence between the carbon-containing dissipative pattern on one side and the carbon-free solid fiber pattern on the opposite side of PHBV / WPU.
[0407] Example 11 employs a double-phase non-collinear path structure, with a maximum carbon-containing projection overlap ratio of 1.4%, minimum cross-surface coverage ratios of 98.1% and 97.9% in the two directions, a minimum common projection width of the terminal corridor of 3.58 mm, and a minimum actual net carbon-containing distance of 5.84 mm between the two sides. Under the preset composite deviation condition, the particles, black transfer, cracks, and delamination in Example 11 are 850±50 per m. -1 1.30±0.12, 9.2±1.0 mm·m -1 And 0.90±0.10%, the corresponding comparative example 10, which did not form a two-way cross surface, was 1240±91 m. -1 ,2.45±0.20,16.8±1.8mm·m -1 The surface resistivity is 1.90±0.17%, and the geometric mean of the surface resistivity is the same for both.
[0408] Both the interdigitated cross-plane anti-overlapping structure and the double-phase non-collinear path structure achieve spatial decoupling between carbon dissipation function and clean edge isolation by reducing the overlapping of carbon-containing pattern projections on both sides and increasing the cross-plane coverage ratio of carbon-free solid fiber patterns on the opposite side.
[0409] Changes in PHBV content:
[0410] The PHBV contents in Examples 2, 1, and 3 were 20 wt%, 28 wt%, and 35 wt%, respectively, with the other main structures and dry coating amounts remaining the same. Under the preset composite deviation condition, the particle release amounts of the three were 1080 particles per m³. -1 920 units / m -1 and 960 m -1 The cracks are 7.2 mm·m. -1 8.0 mm·m -1 and 10.8 mm·m -1 When the PHBV content increased from 20wt% to 28wt%, the particle size decreased. Further increasing it to 35wt% resulted in particle size still lower than the 20wt% group, but increased cracking. All three content levels resulted in a PHBV / WPU terminal structure. The 20wt%–35wt% range was the content range verified by actual measurements in this group. The 28wt% group demonstrated a balance between particle control and bending stability across the three measured content levels.
[0411] Changes in conductive carbon black content:
[0412] The conductive carbon black contents in Examples 4, 1, and 5 were 7 wt%, 9 wt%, and 11 wt%, respectively. Under the preset composite deviation condition, the geometric mean surface resistivity of the three was 7.60 × 10⁻⁶. 8 Ω, 2.80×10 7 Ω and 4.60×10 6 Ω, black transfer ΔL * The values were 1.10±0.08, 1.45±0.09, and 2.15±0.20, respectively, indicating that the surface resistivity decreased while the black transfer increased with the increase of conductive carbon black content. The black transfer ΔL in Comparative Example 12, with a conductive carbon black content of 13 wt%, in Application Examples 1 to 3 is shown. * All values were higher than those in Example 5, which had a conductive carbon black content of 11 wt%, and no simultaneous improvement in cleanliness was observed. The range of conductive carbon black content measured and verified in this group was 7 wt% to 11 wt%.
[0413] Changes in the dry coating amount of the functional layer:
[0414] Examples 6, 1, and 7 respectively verified the lower, middle, and upper combinations of the dry coating amount range of the main functional layer. Under the preset composite deviation state, the particle release amount of the three was 1210 particles / m³. -1 920 units / m -1 and 980 m -1 The crack thicknesses are 10.5 mm·m. -1 8.0 mm·m -1 and 12.6 mm·m -1The lower assembly had higher particle size, while the upper assembly did not continue to decrease particle size, and cracks, delamination, and warping increased. The middle assembly of Example 1 showed a balance between particle control and mechanical stability in this test.
[0415] Variations in region size and spatial parameters:
[0416] In Example 8, the minimum actual net distance between the two carbon-containing surfaces was 4.50 mm, and the particle size under the preset composite deviation state was 1340 ± 88 particles / m. -1 Slightly higher than 1300 m -1 The preset evaluation value indicates that the particle control margin for the lower end of the size combination is relatively small. In Example 9, the minimum actual net carbon distance between the two sides is 8.00 mm, and the particle size is 900 particles / m². -1 However, the total width of the decoupling corridor reached 13.0 mm; Example 10 reduced the particle count to 780 particles per m³ by further reducing carbon-containing projection overlap and increasing the cross-surface coverage ratio. -1 The total width of its decoupling corridor is 11.0 mm.
[0417] In the linkage test of clearance and corridor width, the average values of the smaller clearances on both sides of clearance groups 1 to 5 were 3.00±0.05mm, 4.56±0.03mm, 5.57±0.04mm, 6.58±0.04mm, and 8.08±0.04mm, respectively. With the increase of clearance and corridor width, the overall reduction in particles, black transfer, carbon black hot spots, and cracks was observed. When the average clearance increased from 6.58±0.04mm to 8.08±0.04mm, particles, black transfer, and cracks still improved, but the degree of improvement decreased.
[0418] Application scenarios and parameter trends:
[0419] Tests on the conductive turnover box liner, electronic component insulating sheet, and turnover sleeve showed that the packaging materials can withstand repeated loading and unloading and vibration, reciprocating insertion and removal, damp heat treatment, and bending. When the turnover sleeve is bent perpendicular to the final cut edge of the finished product, the cracks are higher than those in the parallel direction. Placing the fold line within the WPU flexible carbon-free buffer zone can reduce the fold line's continuous penetration through the carbon-containing pattern boundary.
[0420] After the packaging material is combined with the conductive turnover container, the electrostatic dissipation main area forms a conductive connection with the conductive turnover container through the conductive contact portion, and the conductive turnover container is connected to the common grounding point through the grounding connector, thereby forming a system grounding path composed of the electrostatic dissipation main area, the conductive contact portion, the conductive turnover container and the grounding connector.
[0421] Within the tested range of combined parameters, increasing PHBV content resulted in an overall decrease in particle size, but higher content corresponded to an increase in cracks; increasing conductive carbon black content decreased surface resistivity but increased black transfer; increasing the dry coating amount of the functional layer, the width of the carbon-free area, and the actual carbon-containing net distance improved some cleanliness and manufacturing tolerance indicators, but mechanical stability or material usage changed accordingly. Therefore, each parameter was determined comprehensively based on particle size, black transfer, cracks, delamination, surface resistivity, and finished product layout dimensions.
[0422] In summary, this invention sets up an electrostatic dissipation main area, a cross-surface phase-shifting functional mapping transition area, a WPU flexible carbon-free buffer zone, and a PHA / WPU carbon-free terminal corridor on the two main surfaces of a porous fiber paper substrate. This allows the carbon-containing dissipation pattern on one side to be cross-surface-covered by the PHA / WPU carbon-free solid fiber pattern on the opposite side, and ensures that the final cut edge of the finished product is located within the common projection area of the carbon-free terminal corridors on the two main surfaces.
[0423] The listed PHBV examples and comparative examples show that both the interdigitated cross-plane anti-overlay structure and the double-phase non-collinear path structure can be controlled according to the same carbon-containing projection overlap ratio, cross-plane coverage ratio, common projection width, and actual carbon-containing net distance; the combination of cross-plane phase-shifting functional mapping, independent WPU flexible carbon-free buffer zone, and PHA / WPU carbon-free terminal corridor corresponds to lower particle release, black transfer, cracking, and delamination results.
[0424] Those skilled in the art should understand that the above embodiments are merely exemplary and not intended to limit the scope of the invention. The scope of protection of the present invention is defined by the appended claims. Any modifications, equivalent substitutions, improvements, etc., made to the technical solutions of the present invention within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A PHA bio-based antistatic low-dust barrier packaging material for clean isolation of semiconductors and electronic components, comprising a porous fiber paper substrate, said porous fiber paper substrate having a first main surface, a second main surface, and at least one finished product cut edge, characterized in that: The first main surface and the second main surface are respectively provided with a continuous waterborne polyurethane solid fiber sealing bottom layer, an electrostatic dissipation main region formed on the waterborne polyurethane solid fiber sealing bottom layer, and a decoupling corridor located between the electrostatic dissipation main region and the final cut edge of the finished product. The electrostatic dissipation main area contains waterborne polyurethane and conductive carbon black, and forms an in-plane electrostatic dissipation path on the main surface. Each of the decoupling corridors includes, in sequence, a cross-plane phase-shifting functional mapping transition area, a waterborne polyurethane flexible carbon-free buffer zone, and a polyhydroxyalkanoate / waterborne polyurethane carbon-free terminal corridor along the direction from the electrostatic dissipation main area toward the final cut edge of the finished product. The cross-plane phase-shifting functional mapping transition regions of the first main surface and the second main surface are respectively provided with carbon-containing dissipation patterns that are continuously connected to the electrostatic dissipation main region of the main surface, and polyhydroxy fatty acid ester / waterborne polyurethane carbon-free solid fiber patterns located outside the carbon-containing dissipation patterns. The carbon-containing dissipation patterns located on the first main surface and the second main surface are staggered along the extension direction of the final cut edge of the finished product. The carbon-containing dissipation pattern located on the first main surface and the carbon-free polyhydroxyalkanoate / waterborne polyurethane fiber-free pattern located on the second main surface form a cross-face correspondence. The waterborne polyurethane flexible carbon-free buffer zone is composed of the waterborne polyurethane fiber-sealing bottom layer that is not covered by the carbon dissipation pattern and the polyhydroxyalkanoate / waterborne polyurethane carbon-free fiber-fixed pattern, and extends continuously along the extension direction of the final cut edge of the finished product. The polyhydroxyalkanoate / waterborne polyurethane carbon-free terminal corridor extends continuously along the extension direction of the final cut edge of the finished product. The projections of the polyhydroxyalkanoate / waterborne polyurethane carbon-free terminal corridors on the first main surface and the second main surface intersect to form a common projection area on the porous fiber paper substrate. The final cut edge of the finished product is located within the common projection area.
2. The packaging material according to claim 1, characterized in that: After transforming the final dry patterns of the first main surface and the second main surface to a common finished product coordinate system and projecting them onto the mid-surface of the porous fiber paper substrate, the carbon-containing dissipative patterns on the first main surface and the second main surface have a carbon-containing projection overlap ratio of ≤5%, the carbon-containing dissipative patterns on the first main surface have a first-direction cross-surface coverage ratio of ≥95% relative to the polyhydroxyalkanoate / waterborne polyurethane carbon-free solid fiber patterns on the second main surface, and the carbon-containing dissipative patterns on the second main surface have a second-direction cross-surface coverage ratio of ≥95% relative to the polyhydroxyalkanoate / waterborne polyurethane carbon-free solid fiber patterns on the first main surface; The common projection area of the polyhydroxyalkanoate / waterborne polyurethane carbon-free terminal corridor located on the first main surface and the second main surface, formed on the middle surface of the porous fiber paper substrate, has a minimum width ≥1.0 mm measured along the direction from the electrostatic dissipation main area toward the final cut edge of the finished product. The shortest in-plane distance between the final cut edge of the finished product and the nearest area containing conductive carbon black on the first main surface, and the shortest in-plane distance between the final cut edge of the finished product and the nearest area containing conductive carbon black on the second main surface, are both ≥4.5mm.
3. The packaging material according to claim 1, characterized in that: The cross-plane phase-shifting functional mapping transition zone is an interdigitated cross-plane anti-overlapping transition zone; The carbon-containing dissipation pattern located on the first main surface forms a carbon-containing dissipation functional unit on the first main surface, the carbon-containing dissipation pattern located on the second main surface forms a carbon-containing dissipation functional unit on the second main surface, the polyhydroxyalkanoate / waterborne polyurethane carbon-free fiber-fixing pattern located on the first main surface forms a polyhydroxyalkanoate / waterborne polyurethane carbon-free fiber-fixing functional unit on the first main surface, and the polyhydroxyalkanoate / waterborne polyurethane carbon-free fiber-fixing pattern located on the second main surface forms a polyhydroxyalkanoate / waterborne polyurethane carbon-free fiber-fixing functional unit on the second main surface. The first main surface carbon-containing dissipation functional unit and the second main surface polyhydroxy fatty acid ester / waterborne polyurethane carbon-free fiber-fixing functional unit form a first cross-face correspondence relationship, and the second main surface carbon-containing dissipation functional unit and the first main surface polyhydroxy fatty acid ester / waterborne polyurethane carbon-free fiber-fixing functional unit form a second cross-face correspondence relationship. The first main surface carbon dissipation functional unit, the second main surface carbon dissipation functional unit, the first main surface polyhydroxyalkanoate / waterborne polyurethane carbon-free fiber-fixing functional unit, and the second main surface polyhydroxyalkanoate / waterborne polyurethane carbon-free fiber-fixing functional unit are arranged in the same pattern cycle along the extension direction of the final cut edge of the finished product. The first main surface carbon dissipation functional unit and the second main surface carbon dissipation functional unit are staggered along the extension direction of the final cut edge of the finished product, and a common carbon-free interval is maintained on both the first main surface and the second main surface in each pattern cycle, where there is no conductive carbon black on both sides.
4. The packaging material according to claim 1, characterized in that: The cross-plane phase-shifting functional mapping transition region is a double-phase non-collinear path transition region; The carbon-containing dissipation pattern located on the first main surface forms a carbon-containing dissipation path on the first main surface, and the carbon-containing dissipation pattern located on the second main surface forms a carbon-containing dissipation path on the second main surface. The carbon-containing dissipation path on the first main surface and the carbon-containing dissipation path on the second main surface are continuously connected to the electrostatic dissipation main region of their respective main surfaces. The polyhydroxyalkanoate / waterborne polyurethane carbon-free fiber-bonded pattern located on the first main surface forms the polyhydroxyalkanoate / waterborne polyurethane carbon-free fiber-bonded path on the first main surface, and the polyhydroxyalkanoate / waterborne polyurethane carbon-free fiber-bonded pattern located on the second main surface forms the polyhydroxyalkanoate / waterborne polyurethane carbon-free fiber-bonded path on the second main surface. The carbon-containing dissipation path on the first main surface and the carbon-free fiber-fixing path of the polyhydroxyalkanoate / waterborne polyurethane on the second main surface form a first cross-face corresponding path, and the carbon-containing dissipation path on the second main surface and the carbon-free fiber-fixing path of the polyhydroxyalkanoate / waterborne polyurethane on the first main surface form a second cross-face corresponding path. The carbon dissipation path on the first main surface and the carbon dissipation path on the second main surface extend periodically along the extension direction of the final cut edge of the finished product and have a phase difference. After the carbon dissipation path on the first main surface and the carbon dissipation path on the second main surface are projected onto the middle surface of the porous fiber paper substrate and transformed to the common finished product coordinate system, their center lines do not coincide and are not located on the same straight line. The carbon-containing dissipation paths located on the first and second main surfaces are provided between the projections of the carbon-containing paths onto the inner surface of the porous fiber paper substrate, and on the side near the final cut edge of the finished product, with continuous carbon-free areas.
5. The packaging material according to claim 1, characterized in that: The polyhydroxyalkanoate / waterborne polyurethane carbon-free solid fiber pattern contains polyhydroxyalkanoate and waterborne polyurethane, and the polyhydroxyalkanoate / waterborne polyurethane carbon-free terminal corridor includes a polyhydroxyalkanoate / waterborne polyurethane layer formed on the bottom layer of the waterborne polyurethane solid fiber sealing. The polyhydroxy fatty acid ester is a poly(3-hydroxybutyric acid-3-hydroxyvalerate) copolyester; Based on the total polymer solids of the polyhydroxyalkanoate and the waterborne polyurethane, the polyhydroxyalkanoate content in the polyhydroxyalkanoate / waterborne polyurethane carbon-free solid fiber pattern and the polyhydroxyalkanoate / waterborne polyurethane carbon-free terminal corridor is 20wt% to 35wt%, with the remainder being waterborne polyurethane.
6. The packaging material according to claim 1, characterized in that: The carbon-containing dissipation pattern contains waterborne polyurethane and conductive carbon black; based on the total mass of the functional solids of the conductive carbon black and the waterborne polyurethane, the content of the conductive carbon black in the main electrostatic dissipation region and the carbon-containing dissipation pattern is 7wt% to 11wt%, with the remainder being waterborne polyurethane.
7. A method for preparing the packaging material according to claim 1, characterized in that, Includes the following steps: Step 1: Pre-treat the porous fiber paper substrate to form a continuous water-based polyurethane fiber sealing bottom layer on the first main surface and the second main surface, respectively. Step 2: On the waterborne polyurethane fiber-sealing bottom layer of the first main surface and the second main surface, carbon-containing dissipative ink containing waterborne polyurethane and conductive carbon black and polyhydroxy fatty acid ester / waterborne polyurethane carbon-free fiber-sealing ink containing polyhydroxy fatty acid ester and waterborne polyurethane are used to form the electrostatic dissipation main area and the decoupling corridor sequentially or simultaneously. Specifically, the carbon-containing dissipation pattern on each main surface is continuously connected to the electrostatic dissipation main area on the same main surface. The carbon-containing dissipation patterns on the first and second main surfaces are staggered along the extension direction of the final cut edge of the finished product. The carbon-containing dissipation pattern on the first main surface and the polyhydroxyalkanoate / waterborne polyurethane carbon-free solid fiber pattern on the second main surface form a cross-face correspondence. A region is provided on the tangent side of the cross-plane phase-shifting functional mapping transition zone where neither the carbon-containing dissipative ink nor the polyhydroxyalkanoate / waterborne polyurethane carbon-free solid fiber ink is applied, so as to retain the waterborne polyurethane flexible carbon-free buffer zone formed by the waterborne polyurethane solid fiber sealing bottom layer; on the tangent side of the waterborne polyurethane flexible carbon-free buffer zone, the polyhydroxyalkanoate / waterborne polyurethane carbon-free solid fiber ink is used to form the polyhydroxyalkanoate / waterborne polyurethane carbon-free terminal corridor, and the polyhydroxyalkanoate / waterborne polyurethane carbon-free terminal corridor located on the first main surface and the second main surface forms the common projection area. Step 3: Dry the porous fiber paper substrate on which the electrostatic dissipation main region and the decoupling corridor are formed; Step 4: Die-cut or slit within the common projection area to form the final cut edge of the finished product.
8. The preparation method according to claim 7, characterized in that: Before die-cutting or slitting, a double-sided machine vision system is used to collect the final dry patterns of the first main surface and the second main surface, and the final dry patterns of the two main surfaces are converted to a common finished product coordinate system and projected onto the middle surface of the porous fiber paper substrate. Determine the carbon projection overlap ratio of the carbon dissipation patterns on the two main surfaces, determine the first directional cross-surface coverage ratio of the carbon dissipation pattern on the first main surface relative to the polyhydroxyalkanoate / waterborne polyurethane carbon-free solid fiber pattern on the second main surface, and determine the second directional cross-surface coverage ratio of the carbon dissipation pattern on the second main surface relative to the polyhydroxyalkanoate / waterborne polyurethane carbon-free solid fiber pattern on the first main surface. The minimum width of the common projection area measured along the direction from the electrostatic dissipation main area toward the final cut edge of the finished product is taken as the common projection width, and the shortest in-plane distance from the predetermined tangent line corresponding to the final cut edge of the finished product to the nearest actual carbon-containing area on the first main surface and the second main surface is determined respectively. For the porous fiber paper substrate with a carbon-containing projection overlap ratio ≤ 5%, a first-direction cross-surface coverage ratio and a second-direction cross-surface coverage ratio both ≥ 95%, a common projection width ≥ 1.0 mm, and a shortest in-plane distance from the predetermined tangent to the nearest actual carbon-containing area on the first main surface and the second main surface both ≥ 4.5 mm, die-cut or slit along the predetermined tangent located within the common projection area.
9. A packaging system for clean isolation of semiconductors and electronic components, characterized in that, Includes the packaging material, conductive turnover container, at least one conductive contact, and grounding connector as described in claim 1; The packaging material is disposed inside the conductive turnover container; The conductive contact portion is disposed on the side of the packaging material facing the conductive turnover container and located within the main static dissipation area. The main static dissipation area is electrically connected to the conductive turnover container through the conductive contact portion. The conductive container is connected to a common grounding point via the grounding connector, and the electrostatic dissipation main area, the conductive contact portion, the conductive container, and the grounding connector form a system grounding path connected to the common grounding point.
10. The application of the packaging system of claim 9 in the storage, transportation, inter-process handling, or cleanroom isolation of semiconductor devices or electronic components.
Citation Information
Patent Citations
Process for sealing the cutting edges of web-shaped filter material
DE10130919A1
Layered packaging material with an electric conductive layer and process for its manufacture
EP0114802B2
Patterned transparent conductive film based on a random grid
JP5795824B2
Novel paper having low lint and / or anti-static
US20040118538A1
Apparatus and method for producing two-sided patterned webs in registration
US20070141249A1